Quiescence and Coral Biology: Will Warming Waters Result in a New Understanding on Coral Resiliency? - Grace, Sean P. (2018)
The objectives of this sabbatical were to examine the resilience of temperate corals (Astrangia poculata, Ellis & Solander 1787) and to address the following questions: 1. Do corals exhibit quiescence at warmer temperatures?; 2. Does Astrangia poculata exhibit quiescence across their geographic range?; 3. Does the microbial population on corals change during quiescence?; and 4. Does temperature cause a change in symbiotic state in A. poculata?
Keywords: dept.bio; faculty_collection; sabbatical_report

North American Songbirds: Identify the Most Common Songbirds and Hear Their Calls on Your Smartphone - Proctor, Noble S. (Cool Springs Press, 2014)
"Provides information about the habits and habitats of North America's 100 most common birds. Includes information on how to attract birds as well as how to identify their songs with a QR code that links directly to a recording of each bird's song"–
Keywords: Identification; Identification; Birdsongs; North America; Songbirds; dept.bio; faculty_collection

A Field Guide to the Southeast Coast & Gulf of Mexico: Coastal Habitats, Seabirds, Marine Mammals, Fish, & Other Wildlife - Proctor, Noble S. (Yale University Press, 2011)
"This superb book, with its unique focus on the entire marine coastal environment, is the most comprehensive and up-to-date field guide available on the southeastern Atlantic Coast and the Gulf Coast. Not just for beachgoers, the book is essential for birders, whale watchers, fishers, boaters, scuba divers and snorkelers, and shoreline visitors" –Publisher description.
Keywords: Atlantic Coast (South Atlantic States); Coastal animals; Guidebooks; Guidebooks; Atlantic Coast (South Atlantic States); Guidebooks; Coastal ecology; Guidebooks; Marine ecology; Guidebooks; Mexico; Gulf of; Gulf States; Identification; Coastal animals; Identification; Coastal ecology; Identification; Marine animals; Mexico; Gulf of; South Atlantic States; dept.bio; faculty_collection

Variation in seed dormancy quantitative Trait Loci in arabidopsis thaliana originating from one site - Silady, R.A.; Effgen, S.; Koornneef, M.; Reymond, M. (PLoS ONE, 2011)
A Quantitative Trait Locus (QTL) analysis was performed using two novel Recombinant Inbred Line (RIL) populations, derived from the progeny between two Arabidopsis thaliana genotypes collected at the same site in Kyoto (Japan) crossed with the reference laboratory strain Landsberg erecta (Ler). We used these two RIL populations to determine the genetic basis of seed dormancy and flowering time, which are assumed to be the main traits controlling life history variation in Arabidopsis. The analysis revealed quantitative variation for seed dormancy that is associated with allelic variation at the seed dormancy QTL DOG1 (for Delay Of Germination 1) in one population and at DOG6 in both. These DOG QTL have been previously identified using mapping populations derived from accessions collected at different sites around the world. Genetic variation within a population may enhance its ability to respond accurately to variation within and between seasons. In contrast, variation for flowering time, which also segregated within each mapping population, is mainly governed by the same QTL. © 2011 Silady et al.
13 citations (Crossref) [2023-10-31]
Keywords: Arabidopsis; Arabidopsis Proteins; Arabidopsis protein; Arabidopsis thaliana; DOG1 protein; Arabidopsis; Delay Of Germination 1 gene; Delay Of Germination 6 gene; Japan; Plants; Genetically Modified; Quantitative Trait Loci; Seed Dormancy; article; controlled study; dept.bio; flowering; gene mapping; genetic variability; genetics; genotype; nonhuman; peer-reviewed; physiology; plant chromosome; plant gene; quantitative trait locus; recombinant inbred strain; seed dormancy; transgenic plant

Rauisuchia - Nesbitt, S.J.; Brusatte, S.L.; Desojo, J.B.; Liparini, A.; De França, M.A.G.; Weinbaum, J.C.; Gower, D.J. (2013)
'Rauisuchia' comprises Triassic pseudosuchians that ranged greatly in body size, locomotor styles and feeding ecologies. Our concept of what constitutes a rauisuchian is changing as a result of discoveries over the last 15 years. New evidence has shown that rauisuchians are probably not a natural (monophyletic) group, but instead are a number of smaller clades (e.g. Rauisuchidae, Ctenosauriscidae, Shuvosauridae) that may not be each other's closest relatives within Pseudosuchia. Here, we acknowledge that there are still large gaps in the basic understanding in the alphalevel taxonomy and relationships of these groups, but good progress is being made. As a result of renewed interest in rauisuchians, an expanding number of recent studies have focused on the growth, locomotor habits, and biomechanics of these animals, and we review these studies here. We are clearly in the midst of a renaissance in our understanding of rauisuchian evolution and the continuation of detailed descriptions, the development of explicit phylogenetic hypotheses, and explicit palaeobiological studies are essential in advancing our knowledge of these extinct animals. © The Geological Society of London 2013.
Issue: 1 Journal Abbreviation: Geol. Soc. Spec. Publ. Pages: 274 Publication Title: Geol. Soc. Spec. Publ.
Keywords: Triassic; biomechanics; body size; crocodilian; dept.bio; feeding ecology; paleobiology; paleontology; phylogenetics; taxonomy

Hot bats go cold: Heterothermy in neotropical bats - Czenze, Z.J.; Dunbar, M.B. (Canadian Journal of Zoology, 2017)
Torpor is common in bats, but has historically been viewed as an energy-saving technique reserved for temperate and subarctic climates; however, torpor use is common across several tropical bat families. Central America hosts a great diversity of bats with approximately 150 species, yet data from this area are lacking compared with tropical Africa and Australia. We investigated thermoregulatory responses of bats from neotropical Belize and captured adult bats in the tropical forests of Lamanai Archeological Reserve, Belize. After a 12 h acclimation period, we recorded rectal temperature prior to and after exposing bats to an ambient temperature (Ta) of 7 °C forupto 2 h in anenvironmental chamber. All 11 species across four families expressed torpor to some degree upon exposure to cool temperatures. Individuals from Vespertilionidae defended the lowest resting body temperature (Tb) and showed the greatest decrease in Tb after acute exposure to low Ta. Our data help to establish a new spectrum of physiological ability for this group of mammals and shed light on the evolution of torpor and heterothermy. Weshow that energy conservation is important even in warm and energetically stable environmental conditions. Understanding how and why torpor is used in warm climates will help to better define paradigms in physiological ecology. © 2017, Canadian Science Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: Africa; Australia; Bats; Belize; Belize [Central America]; Central America; Heterothermy; Lamanai; Mammalia; Neotropical Region; Orange Walk; Torpor; Tropics; Vespertilionidae; acclimation; bat; body temperature; dept.bio; ecophysiology; energy conservation; environmental conditions; physiological response; thermoregulation; torpor; tropical forest; tropical region

First record of introduction of metacarcinus magister dana, 1852 (Crustacea: Decapoda: Cancridae) and range extension of Eriocheir sinensis Milne-Edwards, 1853 (Crustacea: Decapoda: Varunidae) in the long Island sound - Hudson, D.M.; Schaefer-Padgett, S.; Christie, B.L.; Harris, R. (BioInvasions Records, 2019)
Invasive crustacean species have been present in the Long Island Sound, northwestern Atlantic Ocean, for over two centuries. Three new records of introduction are recorded here from collections by local fishermen. Two records are for male Dungeness crabs, Metacarcinus magister (Dana, 1852), collected in the Western Long Island Sound (2017) and Cape Cod Bay (2018). The other record is that of a range extension documented by a single male Chinese mitten crab, Eriocheir sinensis (Milne-Edwards, 1853), found in New Haven Harbor, Connecticut. Both species could potentially harbor nonnative epibionts and endoparasites. Additionally, E. sinensis may be more likely to establish, as it has in numerous locations in the region and worldwide. © Hudson et al.
0 citations (Crossref) [2023-10-31]
Keywords: Brachyura; Chinese mitten crab; Connecticut; Dungeness crab; Introduced species; Invasive species; Massachusetts; dept.bio; peer-reviewed

Is it time for a new paradigm for systemic cancer treatment? Lessons from a century of cancer chemotherapy. - Crawford, Sarah (Frontiers in pharmacology, 2013)
U.S. SEER (Surveillance Epidemiology and End Results) data for age-adjusted mortality rates for all cancers combined for all races show only a modest overall 13% decline over the past 35 years. Moreover, the greatest contributor to cancer mortality is treatment-resistant metastatic disease. The accepted therapeutic paradigm for the past half-century for the treatment of advanced cancers has involved the use of systemic chemotherapy drugs cytotoxic for cycling cells (both normal and malignant) during DNA synthesis and/or mitosis. The failure of this therapeutic modality to achieve high-level, consistent rates of disease-free survival for some of the most common cancers, including tumors of the lung, colon breast, brain, melanoma, and others is the focus of this paper. A retrospective assessment of critical milestones in cancer chemotherapy indicates that most successful therapeutic regimens use cytotoxic cell cycle inhibitors in combined, maximum tolerated, dose-dense acute treatment regimens originally developed to treat acute lymphoblastic leukemia and some lymphomas. Early clinical successes in this area led to their wholesale application to the treatment of solid tumor malignancies that, unfortunately, has not produced consistent, long-term high cure rates for many common cancers. Important differences in therapeutic sensitivity of leukemias/lymphomas versus solid tumors can be explained by key biological differences that define the treatment-resistant solid tumor phenotype. A review of these clinical outcome data in the context of recent developments in our understanding of drug resistance mechanisms characteristic of solid tumors suggests the need for a new paradigm for the treatment of chemotherapy-resistant cancers. In contrast to reductionist approaches, the systemic approach targets both microenvironmental and systemic factors that drive and sustain tumor progression. These systemic factors include dysregulated inflammatory and oxidation pathways shown to be directly implicated in the development and maintenance of the cancer phenotype. The paradigm stresses the importance of a combined preventive/therapeutic approach involving adjuvant chemotherapies that incorporate anti-inflammatory and anti-oxidant therapeutics.
80 citations (Crossref) [2023-10-31] Place: Switzerland Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University New Haven, CT, USA.
Keywords: Adjuvant; Anti-inflammatory; Anti-oxidant; Chemotherapy; Drug resistance; Neoplasm; Tumor microenvironment; Vinca alkaloid; acute lymphoblastic leukemia; adjuvant therapy; advanced cancer; aminopterin; antibiotic agent; antineoplastic activity; antineoplastic agent; antioxidant; article; bladder cancer; bleomycin; brain cancer; breast cancer; cancer cell; cancer chemotherapy; cancer growth; cancer mortality; cancer recurrence; cancer regression; cancer resistance; cancer survival; carboplatin; carmustine; chemosensitivity; childhood leukemia; chlorambucil; chlormethine; choriocarcinoma; cisplatin; colon cancer; cyclophosphamide; dept.bio; disease activity; disease free survival; doxorubicin; drug intermittent therapy; drug megadose; drug tolerability; drug treatment failure; elastin; etoposide; fludarabine; fluorouracil; gemcitabine; head and neck cancer; human; hydroxyurea; infection; inflammation; leukemia; lung cancer; lymphoma; malignant neoplastic disease; maximum tolerated dose; melanoma; mercaptopurine; metastasis; methotrexate; mitoxantrone; multiple cycle treatment; multiple myeloma; nonhodgkin lymphoma; nonhuman; ovary cancer; ovary carcinoma; paclitaxel; pancreas cancer; phenotype; platinum complex; prednisone; procarbazine; solid tumor; systemic therapy; testis cancer; topotecan; tumor microenvironment; unindexed drug; vinblastine; vinblastine sulfate; vincristine

Encoding human serine phosphopeptides in bacteria for proteome-wide identification of phosphorylation-dependent interactions. - Barber, Karl W; Muir, Paul; Szeligowski, Richard V; Rogulina, Svetlana; Gerstein, Mark; Sampson, Jeffrey R; Isaacs, Farren J; Rinehart, Jesse (Nature biotechnology, 2018)
Post-translational phosphorylation is essential to human cellular processes, but the transient, heterogeneous nature of this modification complicates its study in native systems. We developed an approach to interrogate phosphorylation and its role in protein-protein interactions on a proteome-wide scale. We genetically encoded phosphoserine in recoded E. coli and generated a peptide-based heterologous representation of the human serine phosphoproteome. We designed a single-plasmid library encoding >100,000 human phosphopeptides and confirmed the site-specific incorporation of phosphoserine in >36,000 of these peptides. We then integrated our phosphopeptide library into an approach known as Hi-P to enable proteome-level screens for serine-phosphorylation-dependent human protein interactions. Using Hi-P, we found hundreds of known and potentially new phosphoserine-dependent interactors with 14-3-3 proteins and WW domains. These phosphosites retained important binding characteristics of the native human phosphoproteome, as determined by motif analysis and pull-downs using full-length phosphoproteins. This technology can be used to interrogate user-defined phosphoproteomes in any organism, tissue, or disease of interest.
27 citations (Crossref) [2023-10-31] Place: United States Barber, Karl W. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Barber, Karl W. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Muir, Paul. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Muir, Paul. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven, Connecticut, USA. Szeligowski, Richard V. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Szeligowski, Richard V. Biology Department, Southern Connecticut State University, New Haven, Connecticut, USA. Rogulina, Svetlana. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Rogulina, Svetlana. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Gerstein, Mark. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Gerstein, Mark. Program in Computational Biology and Bioinformatics, Yale University, New Haven, Connecticut, USA. Gerstein, Mark. Department of Molecular Biophysics and Biochemistry, Yale University, New Haven, Connecticut, USA. Gerstein, Mark. Department of Computer Science, Yale University, New Haven, Connecticut, USA. Sampson, Jeffrey R. Agilent Laboratories, Agilent Technologies, Santa Clara, California, USA. Isaacs, Farren J. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Isaacs, Farren J. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven, Connecticut, USA. Rinehart, Jesse. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Rinehart, Jesse. Systems Biology Institute, Yale University, West Haven, Connecticut, USA.
Keywords: *Peptides/ge [Genetics]; *Protein Interaction Maps/ge [Genetics]; *Proteome/ge [Genetics]; *Serine Proteases/ge [Genetics]; 14-3-3 Proteins; 14-3-3 Proteins/ch [Chemistry]; 14-3-3 Proteins/ge [Genetics]; 14-3-3 proteins; Amino Acid Motifs; Amino Acid Motifs/ge [Genetics]; Amino acids; Article; Binding characteristics; Cellular process; DNA library; Encoding (symbols); Enzyme activity; Escherichia coli; Escherichia coli/ge [Genetics]; Gene Library; Human proteins; Humans; Motif analysis; Peptides; Peptides/ch [Chemistry]; Phosphopeptides; Phosphoproteomes; Phosphorylation; Phosphoserine; Phosphoserine/ch [Chemistry]; Plasmids; Plasmids/ge [Genetics]; Protein Interaction Maps; Protein-protein interactions; Proteome; Serine Proteases; Serine Proteases/ch [Chemistry]; Signal encoding; WW Domains; WW Domains/ge [Genetics]; WW domain; amino terminal sequence; assay; carboxy terminal sequence; cell lysate; chemistry; controlled study; dept.bio; fluorescence activated cell sorting; fusion protein; gene library; genetics; high throughput sequencing; human; immunoblotting; immunoprecipitation; in vitro study; ligand binding; mass spectrometry; nonhuman; peer-reviewed; peptide; peptide library; phosphopeptide; phosphorylation; phosphoserine; plasmid; priority journal; protein 14 3 3; protein analysis; protein degradation; protein motif; protein phosphorylation; protein protein interaction; proteome; proteomics; pull down assay; serine; serine proteinase; transcription factor FKHRL1; transfer RNA

Postnatal development of NT3 and TrkC in mouse ventral cochlear nucleus. - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2010)
In the developing nervous system, neurotrophin 3 (NT3) and brain-derived neurotrophic factor (BDNF) have been shown to interact with each other and with different parts of a neuron or glia and over considerable distances in time and space. The auditory system provides a useful model for analyzing these events, insofar as it is subdivided into well-defined groups of specific neuronal types that are readily related to each other at each stage of development. Previous work in our laboratory suggested that NT3 and its receptor TrkC in the mouse cochlear nucleus (CN) may be involved in directing neuronal migration and initial targeting of inputs from cochlear nerve axons in the embryo. NT3 is hard to detect soon after birth, but TrkC lingers longer. Here we found NT3 and TrkC around P8 and the peak around P30. Prominent in ventral CN, associated with globular bushy cells and stellate cells, they were localized to different subcellular sites. The TrkC immunostain was cytoplasmic, and that of NT3 was axonal and perisomatic. TrkC may be made by CN neurons, whereas NT3 has a cochlear origin. The temporal pattern of their development and the likelihood of activity-dependent release of NT3 from cochlear axons suggest that it may not be critical in early synaptogenesis; it may provide long-term trophic effects, including stabilization of synapses once established. Activity-related regulation could coordinate the supply of NT3 with inner ear activity. This may require interaction with other neurotrophins, such as BDNF.
9 citations (Crossref) [2023-10-31] Place: United States Feng, J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Neurons/me [Metabolism]; *Neurotrophin 3/me [Metabolism]; *Receptor; trkC/me [Metabolism]; Age Factors; Animals; Cochlear Nucleus; Fluorescent Antibody Technique; Gene Expression Regulation; Developmental; Mice; Microscopy; Fluorescence; NT3; Neurons; Neurotrophin 3; Postnatal development; Receptor; trkC; TrkC; Ventral cochlear nucleus (VCN); animal cell; animal experiment; article; brain derived neurotrophic factor; cellular distribution; cochlear nerve; cochlear nucleus; controlled study; cytoplasm; dept.bio; embryo; female; immunohistochemistry; inner ear; male; mouse; nerve cell; nerve fiber; nerve root; neurotrophin 3; neurotrophin 3 receptor; nonhuman; postnatal development; priority journal; protein interaction; regulatory mechanism; stellate cell; synapse; synaptogenesis

Degeneration in the ventral cochlear nucleus after severe noise damage in mice - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2012)
To study the mechanisms of noise-induced hearing loss and the phantom noise, or tinnitus, often associated with it, we used a mouse model of noise damage designed for reproducible and quantitative structural analyses. We selected the posteroventral cochlear nucleus, which has shown considerable plasticity in past studies, and correlated its changes with the distribution of neurotrophin 3 (NT3). We used volume change, optical density analysis, and microscopic cluster analysis to measure the degeneration after noise exposure. There was a fluctuation pattern in the reorganization of nerve terminals. The data suggest that the source and size of the nerve terminals affect their capacity for regeneration. We hypothesize that the deafferentation of ventral cochlear nucleus is the structural basis of noise-induced tinnitus. In addition, the immunofluorescent data show a possible connection between NT3 and astrocytes. There appears to be a compensatory process in the supporting glial cells during this degeneration. Glia may play a role in the mechanisms of noise-induced hearing loss. © 2011 Wiley Periodicals, Inc.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-539-907-848-327 tex.type: [object Object]
Keywords: Analysis of Variance; Animals; Calcium-Binding Proteins; Cluster Analysis; Cochlea; Cochlear Nucleus; Disease Models; Animal; Excitatory Amino Acid Transporter 2; Hearing Loss; Sensorineural; Hearing loss; Membrane Glycoproteins; Mice; Mice; Inbred C57BL; Mouse model; NT3; Nerve Growth Factors; Nerve Tissue Proteins; Neurodegenerative Diseases; Noise; Time Factors; Tinnitus; animal cell; animal experiment; animal model; animal tissue; article; astrocyte; controlled study; deafferentation; dept.bio; disease severity; environmental exposure; glia cell; hearing loss; immunofluorescence; mouse; nerve cell plasticity; nerve degeneration; nerve ending; nerve regeneration; neurotrophin 3; noise; nonhuman; optical density; posteroventral cochlear nucleus; priority journal; quantitative analysis; tinnitus

Rhizosphere microbiome selection by Epichloë endophytes of Festuca arundinacea - Roberts, Elizabeth Lewis; Ferraro, Aileen (Plant and Soil, 2015)
Aims: Loline alkaloids produced by Epichloë spp. are known to deter feeding by insect herbivores while also serving as a significant carbon source for certain epiphytic bacteria on tall fescue leaves. In this study we examined the role of loline alkaloids in attracting certain bacteria to the rhizosphere of tall fescue plants that harbor loline producing fungal endophytes. Methods: Population studies were used to compare the fitness of known loline catabolizing strains to other rhizosphere bacteria. Pyrosequencing of 16S rRNA fragments compared the composition of bacterial communities inhabiting the endophyte infected tall fescue (Festuca arundinacea) rhizosphere to those of endophyte free fescue plants. Results: Rhizosphere population studies demonstrated that loline catabolizing strains Burkholderia ambifaria 7R and Pseudomonas aureofaciens outcompete and suppress the growth of non-loline catabolizing strains. Pyrosequencing of 16S rRNA fragments showed greater percentages of certain plant growth promoting bacteria in rhizosperes seeded with B. ambifaria 7R than non-inoculated soils. Rhizospheres of endophyte infected plants showed higher species richness (Shannon diversity index = 4.03) over endophyte free rhizospheres (Shannon diversity index = 3.08) and a greater percentage of Firmicutes. Conclusions: The differences in microbial community composition between endophyte-infected and endophyte-free rhizospheres suggest that the presence of fungal endophytes influences microbial community structure. Loline alkaloid production may be one proxy by which the fungal endophyte shapes microbial communities, as evidenced by increased fitness of loline catabolizing bacteria in the tall fescue rhizosphere. © 2015, Springer International Publishing Switzerland.
21 citations (Crossref) [2023-10-31] Citation Key Alias: pop00270 tex.type: [object Object]
Keywords: Bacteria (microorganisms); Burkholderia ambifaria; Endophyte; Epichloë spp; Festuca arundinacea; Firmicutes; Hexapoda; Loline alkaloids; Pseudomonas chlororaphis; Tall fescue; alkaloid; antifeedant; bacterium; community structure; dept.bio; diversity index; endophyte; fitness; fungus; grass; insect; microbial community; microorganism; rhizosphere; species richness

Designing a broad-spectrum integrative approach for cancer prevention and treatment. - Block, Keith I; Gyllenhaal, Charlotte; Lowe, Leroy; Amedei, Amedeo; Amin, A R M Ruhul; Amin, Amr; Aquilano, Katia; Arbiser, Jack; Arreola, Alexandra; Arzumanyan, Alla; Ashraf, S Salman; Azmi, Asfar S; et al. (Seminars in Cancer Biology, 2015)
Targeted therapies and the consequent adoption of "personalized" oncology have achieved notable successes in some cancers; however, significant problems remain with this approach. Many targeted therapies are highly toxic, costs are extremely high, and most patients experience relapse after a few disease-free months. Relapses arise from genetic heterogeneity in tumors, which harbor therapy-resistant immortalized cells that have adopted alternate and compensatory pathways (i.e., pathways that are not reliant upon the same mechanisms as those which have been targeted). To address these limitations, an international task force of 180 scientists was assembled to explore the concept of a low-toxicity "broad-spectrum" therapeutic approach that could simultaneously target many key pathways and mechanisms. Using cancer hallmark phenotypes and the tumor microenvironment to account for the various aspects of relevant cancer biology, interdisciplinary teams reviewed each hallmark area and nominated a wide range of high-priority targets (74 in total) that could be modified to improve patient outcomes. For these targets, corresponding low-toxicity therapeutic approaches were then suggested, many of which were phytochemicals. Proposed actions on each target and all of the approaches were further reviewed for known effects on other hallmark areas and the tumor microenvironment. Potential contrary or procarcinogenic effects were found for 3.9% of the relationships between targets and hallmarks, and mixed evidence of complementary and contrary relationships was found for 7.1%. Approximately 67% of the relationships revealed potentially complementary effects, and the remainder had no known relationship. Among the approaches, 1.1% had contrary, 2.8% had mixed and 62.1% had complementary relationships. These results suggest that a broad-spectrum approach should be feasible from a safety standpoint. This novel approach has potential to be relatively inexpensive, it should help us address stages and types of cancer that lack conventional treatment, and it may reduce relapse risks. A proposed agenda for future research is offered. Copyright © 2015 The Authors. Published by Elsevier Ltd.. All rights reserved.
196 citations (Crossref) [2023-10-31] Place: England Block, Keith I. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Electronic address: drblock@blockmedical.com. Gyllenhaal, Charlotte. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Lowe, Leroy. Getting to Know Cancer, Truro, Nova Scotia, Canada; Lancaster Environment Centre, Lancaster University, Bailrigg, Lancaster, United Kingdom. Electronic address: Leroy.lowe@gettingtoknowcancer.org. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Amin, A R M Ruhul. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Amin, Amr. Department of Biology, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Arbiser, Jack. Winship Cancer Institute of Emory University, Atlanta, GA, United States; Atlanta Veterans Administration Medical Center, Atlanta, GA, United States; Department of Dermatology, Emory University School of Medicine, Emory University, Atlanta, GA, United States. Arreola, Alexandra. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Arzumanyan, Alla. Department of Biology, Temple University, Philadelphia, PA, United States. Ashraf, S Salman. Department of Chemistry, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Azmi, Asfar S. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Bilsland, Alan. University of Glasgow, Glasgow, United Kingdom. Bishayee, Anupam. Department of Pharmaceutical Sciences, College of Pharmacy, Larkin Health Sciences Institute, Miami, FL, United States. Blain, Stacy W. Department of Pediatrics, State University of New York, Downstate Medical Center, Brooklyn, NY, United States. Block, Penny B. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Boosani, Chandra S. Department of BioMedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Carey, Thomas E. Head and Neck Cancer Biology Laboratory, University of Michigan, Ann Arbor, MI, United States. Carnero, Amancio. Instituto de Biomedicina de Sevilla, Consejo Superior de Investigaciones Cientificas, Seville, Spain. Carotenuto, Marianeve. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy. Casey, Stephanie C. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Chakrabarti, Mrinmay. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Chaturvedi, Rupesh. School of Biotechnology, Jawaharlal Nehru University, New Delhi, India. Chen, Georgia Zhuo. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Chen, Helen. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Chen, Yi Charlie. Department of Biology, Alderson Broaddus University, Philippi, WV, United States. Choi, Beom K. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Coley, Helen M. Faculty of Health and Medical Sciences, University of Surrey, Guildford, Surrey, United Kingdom. Collins, Andrew R. Department of Nutrition, Faculty of Medicine, University of Oslo, Oslo, Norway. Connell, Marisa. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, New Haven, CT, United States. Curran, Colleen S. School of Medicine and Public Health, University of Wisconsin-Madison, Madison, WI, United States. Dabrosin, Charlotta. Department of Oncology and Department of Clinical and Experimental Medicine, Linkoping University, Linkoping, Sweden. Damia, Giovanna. Department of Oncology, Istituto Di Ricovero e Cura a Carattere Scientifico - Istituto di Ricerche Farmacologiche Mario Negri, Milan, Italy. Dasgupta, Santanu. Department of Cellular and Molecular Biology, the University of Texas Health Science Center at Tyler, Tyler, TX, United States. DeBerardinis, Ralph J. Children's Medical Center Research Institute, University of Texas - Southwestern Medical Center, Dallas, TX, United States. Decker, William K. Department of Pathology & Immunology, Baylor College of Medicine, Houston, TX, United States. Dhawan, Punita. Department of Surgery and Cancer Biology, Division of Surgical Oncology, Vanderbilt University School of Medicine, Nashville, TN, United States. Diehl, Anna Mae E. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Dong, Jin-Tang. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Dou, Q Ping. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Drew, Janice E. Rowett Institute of Nutrition and Health, University of Aberdeen, Aberdeen, Scotland, United Kingdom. Elkord, Eyad. College of Medicine & Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates. El-Rayes, Bassel. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Feitelson, Mark A. Department of Biology, Temple University, Philadelphia, PA, United States. Felsher, Dean W. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Ferguson, Lynnette R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Fimognari, Carmela. Dipartimento di Scienze per la Qualita della Vita Alma Mater Studiorum-Universita di Bologna, Rimini, Italy. Firestone, Gary L. Department of Molecular & Cell Biology, University of California Berkeley, Berkeley, CA, United States. Frezza, Christian. Medical Research Council Cancer Unit, University of Cambridge, Hutchison/MRC Research Centre, Cambridge, United Kingdom. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Fuster, Mark M. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Generali, Daniele. Department of Medical, Surgery and Health Sciences, University of Trieste, Trieste, Italy; Molecular Therapy and Pharmacogenomics Unit, Azienda Ospedaliera Istituti Ospitalieri di Cremona, Cremona, Italy. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Gieseler, Frank. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Gilbertson, Michael. Getting to Know Cancer, Guelph, Canada. Green, Michelle F. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Grue, Brendan. Departments of Environmental Science, Microbiology and Immunology, Dalhousie University, Halifax, Nova Scotia, Canada. Guha, Gunjan. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Halicka, Dorota. Department of Pathology, New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana Champaign, Champaign, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Hentosh, Patricia. School of Medical Laboratory and Radiation Sciences, Old Dominion University, Norfolk, VA, United States. Hirschey, Matthew D. Department of Medicine, Duke University Medical Center, Durham, NC, United States; Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Hofseth, Lorne J. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Holcombe, Randall F. Tisch Cancer Institute, Mount Sinai School of Medicine, New York, NY, United States. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Hsu, Hsue-Yin. Department of Life Sciences, Tzu-Chi University, Hualien, Taiwan. Huang, Gloria S. Albert Einstein College of Medicine and Montefiore Medical Center, Bronx, NY, United States. Jensen, Lasse D. Department of Medical and Health Sciences, Linkoping University, Linkoping, Sweden; Department of Microbiology, Tumor and Cell Biology, Karolinska Institutet, Stockholm, Sweden. Jiang, Wen G. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Jones, Lee W. Department of Medicine, Memorial Sloan-Kettering Cancer Center, New York, NY, United States. Karpowicz, Phillip A. University of Windsor, Windsor, Ontario, Canada. Keith, W Nicol. University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Laboratory Medicine and Pathology, Mayo Clinic, Rochester, MN, United States. Khan, Gazala N. Henry Ford Hospital, Detroit, MI, United States. Khatami, Mahin. Inflammation and Cancer Research, National Cancer Institute (Retired), National Institutes of Health, Bethesda, MD, United States. Ko, Young H. University of Maryland BioPark, Innovation Center, KoDiscovery, Baltimore, MD, United States. Kucuk, Omer. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Kulathinal, Rob J. Department of Biology, Temple University, Philadelphia, PA, United States. Kumar, Nagi B. Moffitt Cancer Center, University of South Florida College of Medicine, Tampa, FL, United States. Kwon, Byoung S. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea; Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Le, Anne. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Lea, Michael A. New Jersey Medical School, Rutgers University, Newark, NJ, United States. Lee, Ho-Young. College of Pharmacy, Seoul National University, South Korea. Lichtor, Terry. Department of Neurosurgery, Rush University Medical Center, Chicago, IL, United States. Lin, Liang-Tzung. Department of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan. Locasale, Jason W. Division of Nutritional Sciences, Cornell University, Ithaca, NY, United States. Lokeshwar, Bal L. Department of Medicine, Georgia Regents University Cancer Center, Augusta, GA, United States. Longo, Valter D. Andrus Gerontology Center, Division of Biogerontology, University of Southern California, Los Angeles, CA, United States. Lyssiotis, Costas A. Department of Molecular and Integrative Physiology and Department of Internal Medicine, Division of Gastroenterology, University of Michigan, Ann Arbor, MI, United States. MacKenzie, Karen L. Children's Cancer Institute Australia, Kensington, New South Wales, Australia. Malhotra, Meenakshi. Department of Biomedical Engineering, McGill University, Montreal, Canada. Marino, Maria. Department of Science, University Roma Tre, Rome, Italy. Martinez-Chantar, Maria L. Metabolomic Unit, Centro de Investigacion Biomedica en Red de Enfermedades Hepaticas y Digestivas, Technology Park of Bizkaia, Bizkaia, Spain. Matheu, Ander. Biodonostia Institute, Gipuzkoa, Spain. Maxwell, Christopher. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. McDonnell, Eoin. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Meeker, Alan K. Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Mehrmohamadi, Mahya. Field of Genetics, Genomics, and Development, Department of Molecular Biology and Genetics, Cornell University, Ithaca, NY, United States. Mehta, Kapil. Department of Experimental Therapeutics, University of Texas MD Anderson Cancer Center, Houston, TX, United States. Michelotti, Gregory A. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Mohammad, Ramzi M. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Morre, D James. Mor-NuCo, Inc, Purdue Research Park, West Lafayette, IN, United States. Muralidhar, Vinayak. Harvard-MIT Division of Health Sciences and Technology, Harvard Medical School, Boston, MA, United States; Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Muqbil, Irfana. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Murphy, Michael P. MRC Mitochondrial Biology Unit, Wellcome Trust-MRC Building, Hills Road, Cambridge, United Kingdom. Nagaraju, Ganji Purnachandra. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Nahta, Rita. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Panis, Carolina. Laboratory of Inflammatory Mediators, State University of West Parana, UNIOESTE, Parana, Brazil. Pantano, Francesco. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Parslow, Virginia R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Pawelec, Graham. Center for Medical Research, University of Tubingen, Tubingen, Germany. Pedersen, Peter L. Departments of Biological Chemistry and Oncology, Member at Large, Sidney Kimmel Comprehensive Cancer Center, Johns Hopkins University, School of Medicine, Baltimore, MD, United States. Poore, Brad. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Poudyal, Deepak. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Prakash, Satya. Department of Biomedical Engineering, McGill University, Montreal, Canada. Prince, Mark. Department of Otolaryngology-Head and Neck, Medical School, University of Michigan, Ann Arbor, MI, United States. Raffaghello, Lizzia. Laboratory of Oncology, Istituto Giannina Gaslini, Genoa, Italy. Rathmell, Jeffrey C. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Rathmell, W Kimryn. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Ray, Swapan K. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Reichrath, Jorg. Center for Clinical and Experimental Photodermatology, Clinic for Dermatology, Venerology and Allergology, The Saarland University Hospital, Homburg, Germany. Rezazadeh, Sarallah. Department of Biology, University of Rochester, Rochester, NY, United States. Ribatti, Domenico. Department of Basic Medical Sciences, Neurosciences and Sensory Organs, University of Bari Medical School, Bari, Italy & National Cancer Institute Giovanni Paolo II, Bari, Italy. Ricciardiello, Luigi. Department of Medical and Surgical Sciences, University of Bologna, Bologna, Italy. Robey, R Brooks. White River Junction Veterans Affairs Medical Center, White River Junction, VT, United States; Geisel School of Medicine at Dartmouth, Hanover, NH, United States. Rodier, Francis. Centre de Rechercher du Centre Hospitalier de l'Universite de Montreal and Institut du Cancer de Montreal, Montreal, Quebec, Canada; Universite de Montreal, Departement de Radiologie, Radio-Oncologie et Medicine Nucleaire, Montreal, Quebec, Canada. Rupasinghe, H P Vasantha. Department of Environmental Sciences, Faculty of Agriculture and Department of Pathology, Faculty of Medicine, Dalhousie University, Halifax, Nova Scotia, Canada. Russo, Gian Luigi. Institute of Food Sciences National Research Council, Avellino, Italy. Ryan, Elizabeth P. Department of Environmental and Radiological Health Sciences, Colorado State University, Fort Collins, CO, United States. Samadi, Abbas K. Sanus Biosciences, San Diego, CA, United States. Sanchez-Garcia, Isidro. Experimental Therapeutics and Translational Oncology Program, Instituto de Biologia Molecular y Celular del Cancer, CSIC-Universidad de Salamanca, Salamanca, Spain. Sanders, Andrew J. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Santini, Daniele. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Sarkar, Malancha. Department of Biology, University of Miami, Miami, FL, United States. Sasada, Tetsuro. Department of Immunology, Kurume University School of Medicine, Kurume, Fukuoka, Japan. Saxena, Neeraj K. Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, United States. Shackelford, Rodney E. Department of Pathology, Louisiana State University, Health Shreveport, Shreveport, LA, United States. Shantha Kumara, H M C. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Sharma, Dipali. Department of Oncology, Johns Hopkins University School of Medicine and the Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins, Baltimore, MD, United States. Shin, Dong M. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Sidransky, David. Department of Otolaryngology-Head and Neck Surgery, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Siegelin, Markus David. Department of Pathology and Cell Biology, Columbia University Medical Center, New York, NY, United States. Signori, Emanuela. National Research Council, Institute of Translational Pharmacology, Rome, Italy. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Sivanand, Sharanya. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Sliva, Daniel. DSTest Laboratories, Purdue Research Park, Indianapolis, IN, United States. Smythe, Carl. Department of Biomedical Science, Sheffield Cancer Research Centre, University of Sheffield, Sheffield, United Kingdom. Spagnuolo, Carmela. Institute of Food Sciences National Research Council, Avellino, Italy. Stafforini, Diana M. Huntsman Cancer Institute and Department of Internal Medicine, University of Utah, Salt Lake City, UT, United States. Stagg, John. Centre de Recherche du Centre Hospitalier de l'Universite de Montreal, Faculte de Pharmacie et Institut du Cancer de Montreal, Montreal, Quebec, Canada. Subbarayan, Pochi R. Department of Medicine, University of Miami Miller School of Medicine, Miami, FL, United States. Sundin, Tabetha. Department of Molecular Diagnostics, Sentara Healthcare, Norfolk, VA, United States. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Thompson, Sarah K. Department of Surgery, Royal Adelaide Hospital, Adelaide, Australia. Tran, Phuoc T. Departments of Radiation Oncology & Molecular Radiation Sciences, Oncology and Urology, Johns Hopkins School of Medicine, Baltimore, MD, United States. Ungefroren, Hendrik. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Vander Heiden, Matthew G. Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Venkateswaran, Vasundara. Department of Surgery, University of Toronto, Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Vinay, Dass S. Section of Clinical Immunology, Allergy, and Rheumatology, Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Vlachostergios, Panagiotis J. Department of Internal Medicine, New York University Lutheran Medical Center, Brooklyn, New York, NY, United States. Wang, Zongwei. Department of Urology, Massachusetts General Hospital, Harvard Medical School, Boston, MA, United States. Wellen, Kathryn E. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Whelan, Richard L. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Yang, Eddy S. Department of Radiation Oncology, University of Alabama at Birmingham School of Medicine, Birmingham, AL, United States. Yang, Huanjie. The School of Life Science and Technology, Harbin Institute of Technology, Harbin, Heilongjiang, China. Yang, Xujuan. University of Illinois at Urbana Champaign, Champaign, IL, United States. Yaswen, Paul. Life Sciences Division, Lawrence Berkeley National Lab, Berkeley, CA, United States. Yedjou, Clement. Department of Biology, Jackson State University, Jackson, MS, United States. Yin, Xin. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Zhu, Jiyue. Washington State University College of Pharmacy, Spokane, WA, United States. Zollo, Massimo. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy.
Keywords: *Genetic Heterogeneity; *Molecular Targeted Therapy; *Neoplasms/th [Therapy]; *Precision Medicine; Antineoplastic Agents; Phytogenic; Antineoplastic Agents; Phytogenic/tu [Therapeutic Use]; Cancer hallmarks; Drug Resistance; Neoplasm; Drug Resistance; Neoplasm/ge [Genetics]; Genetic Heterogeneity; Humans; Integrative medicine; Molecular Targeted Therapy; Multi-targeted; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pa [Pathology]; Neoplasms/pc [Prevention & Control]; Phytochemicals; Precision Medicine; Review; Signal Transduction; Targeted therapy; Tumor Microenvironment; Tumor Microenvironment/ge [Genetics]; anthocyanin; antineoplastic activity; antineoplastic agent; apoptosis; belinostat; berberine; breast cancer; cancer prevention; cancer therapy; cell immortalization; colorectal cancer; curcumin; deguelin; dept.bio; dietary intake; dinaciclib; drug cost; drug efficacy; drug resistance; drug safety; drug targeting; enterolactone; epigallocatechin gallate; gamma linolenic acid; genetic heterogeneity; genetics; genistein; genomic instability; gossypol; human; icosapentaenoic acid; imetelstat; inflammation; integrative medicine; interdisciplinary communication; kaempferol; luteolin; lycopene; melatonin; metastasis; metastasis inhibition; molecularly targeted therapy; naringenin; natural product; nonhuman; palbociclib; patent; pathology; perillyl alcohol; personalized medicine; phenotype; phytochemistry; recurrence risk; resveratrol; risk reduction; romidepsin; selinexor; signal transduction; silibinin; soybean; triptolide; tumor escape; tumor invasion; tumor microenvironment; tumor vascularization; unindexed drug; vorinostat; withaferin A; zerumbone

Cancer prevention and therapy through the modulation of the tumor microenvironment. - Casey, Stephanie C; Amedei, Amedeo; Aquilano, Katia; Azmi, Asfar S; Benencia, Fabian; Bhakta, Dipita; Bilsland, Alan E; Boosani, Chandra S; Chen, Sophie; Ciriolo, Maria Rosa; Crawford, Sarah; Fujii, Hiromasa; et al. (Seminars in Cancer Biology, 2015)
Cancer arises in the context of an in vivo tumor microenvironment. This microenvironment is both a cause and consequence of tumorigenesis. Tumor and host cells co-evolve dynamically through indirect and direct cellular interactions, eliciting multiscale effects on many biological programs, including cellular proliferation, growth, and metabolism, as well as angiogenesis and hypoxia and innate and adaptive immunity. Here we highlight specific biological processes that could be exploited as targets for the prevention and therapy of cancer. Specifically, we describe how inhibition of targets such as cholesterol synthesis and metabolites, reactive oxygen species and hypoxia, macrophage activation and conversion, indoleamine 2,3-dioxygenase regulation of dendritic cells, vascular endothelial growth factor regulation of angiogenesis, fibrosis inhibition, endoglin, and Janus kinase signaling emerge as examples of important potential nexuses in the regulation of tumorigenesis and the tumor microenvironment that can be targeted. We have also identified therapeutic agents as approaches, in particular natural products such as berberine, resveratrol, onionin A, epigallocatechin gallate, genistein, curcumin, naringenin, desoxyrhapontigenin, piperine, and zerumbone, that may warrant further investigation to target the tumor microenvironment for the treatment and/or prevention of cancer. Copyright © 2015 Elsevier Ltd. All rights reserved.
242 citations (Crossref) [2023-10-31] Place: England Casey, Stephanie C. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Azmi, Asfar S. Department of Oncology, Wayne State University School of Medicine, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Bilsland, Alan E. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Boosani, Chandra S. Department of Biomedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Crawford, Sarah. Department of Biology, Southern Connecticut State University, New Haven, CT, United States. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Guha, Gunjan. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Halicka, Dorota. New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Keith, W Nicol. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Center for Cancer Research, National Cancer Institute, National Institutes of Health, Bethesda, MD, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Vasantha Rupasinghe, H P. Department of Environmental Sciences, Faculty of Agriculture, Dalhousie University, Nova Scotia, Canada. Samadi, Abbas. Sanus Biosciences, San Diego, United States. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Venkateswaran, Vasundara. Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Whelan, Richard L. Mount Sinai Roosevelt Hospital, Icahn Mount Sinai School of Medicine, New York City, NY, United States. Yang, Xujuan. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Felsher, Dean W. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Electronic address: dfelsher@stanford.edu.
Keywords: *Carcinogenesis/de [Drug Effects]; *Neoplasms/dt [Drug Therapy]; *Neovascularization; Pathologic/dt [Drug Therapy]; *Tumor Microenvironment/ge [Genetics]; 5 chloro n2 [1 (5 fluoro 2 pyrimidinyl)ethyl] n4 (5 methyl 1h pyrazol 3 yl) 2; 4 pyrimidinediamine; Antineoplastic Agents; Antineoplastic Agents/tu [Therapeutic Use]; Cancer biology; Cancer prevention; Cancer therapy; Carcinogenesis; Carcinogenesis/ge [Genetics]; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Humans; Janus kinase; Molecular Targeted Therapy; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pc [Prevention & Control]; Neovascularization; Pathologic; Neovascularization; Pathologic/ge [Genetics]; Neovascularization; Pathologic/pc [Prevention & Control]; Review; Signal Transduction; Tumor Microenvironment; Tumor Microenvironment/de [Drug Effects]; Tumor microenvironment; antiinflammatory activity; antineoplastic agent; antioxidant activity; antiproliferative activity; apoptosis; bacterial infection; berberine; bevacizumab; cancer prevention; cancer therapy; candidiasis; carcinogenesis; cell proliferation; cholesterol synthesis; cisplatin; colorectal cancer; curcumin; cytokine production; dendritic cell; dept.bio; desoxyrhapontigenin; drug cytotoxicity; drug effects; drug potentiation; drug structure; drug targeting; endoglin; epigallocatechin gallate; fatty liver; fibrosis; genetics; genistein; genomic instability; glioblastoma; human; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypercholesterolemia; hyperlipidemia; hypoxia; indoleamine 2; 3 dioxygenase; interleukin 6; kidney cancer; liver cancer; liver cell carcinoma; lung cancer; lung metastasis; macrophage activation; metastasis inhibition; molecularly targeted therapy; mycosis; naringenin; natural product; non insulin dependent diabetes mellitus; nonhuman; obesity; oncogene; onionin A; paclitaxel; pancreas tumor; parasitosis; piperine; reactive oxygen metabolite; resveratrol; signal transduction; sorafenib; stomach cancer

On the origins of autism: The Quantitative Threshold Exposure hypothesis. - Crawford, S (Medical hypotheses, 2015)
The Quantitative Threshold Exposure (QTE) hypothesis is a multifactorial threshold model that accounts for the cumulative effects of risk factor exposure in both the causation of autism spectrum disorder (ASD) and its dramatic increase over the past 30 years. The QTE hypothesis proposes that ASD is triggered by the cumulative effects of high-level exposure to endogenous and environmental factors that act as antigens to impair normal immune system (IS) and associated central nervous system (CNS) functions during critical developmental stages. The quantitative threshold parameters that comprise a cumulative risk for the development of ASD are identified by the assessment of documented epidemiological factors that, in sum, determine the likelihood that ASD will occur as a result of their effects on critically integrated IS and CNS pathways active during prenatal, neo-natal and early childhood brain maturation. The model proposes an explanation for the relationship between critical developmental stages of brain/immune system development in conjunction with the quantitative effects of genetic and environmental risk factors that may interface with these critical developmental windows. This model may be useful even when the individual contributions of specific risk factors cannot be quantified, as it proposes that the combined quantitative level of exposure to risk factors for ASD rather than exposure to any one risk factor per se defines threshold occurrence rates. Copyright © 2015 Elsevier Ltd. All rights reserved.
10 citations (Crossref) [2023-10-31] Place: United States Crawford, S. Department of Biology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: crawfords2@southernct.edu.
Keywords: *Autistic Disorder/ep [Epidemiology]; *Environmental Exposure/sn [Statistics & Numerical Data]; *Epidemiologic Methods; *Risk Assessment/mt [Methods]; *Threshold Limit Values; 5 HTT gene; 5 hydroxytryptophan; Article; Autistic Disorder; Causality; DNA polymorphism; Environmental Exposure; Epidemiologic Methods; Evidence-Based Medicine; Humans; Incidence; RLN gene; Risk Assessment; Threshold Limit Values; autism; autoimmune disease; brain dysfunction; brain maturation; cannabinoid 1 receptor; cannabinoid 2 receptor; cannabis use; central nervous system function; childhood disease; childhood feeding; copy number variation; dept.bio; developmental stage; disease association; disease severity; environmental exposure; environmental factor; epidemiological data; evidence based medicine; feeding; feeding behavior; genetic association; genetic predisposition; genetic risk; high risk population; human; hypothesis; immunoreactivity; incidence; infant feeding; intrauterine infection; n acetylgalactosaminidase; nervous system development; nonbiological model; nonhuman; pediatric infectious disease; perinatal period; prevalence; procedures; quantitative threshold exposure hypothesis; reelin; risk assessment; risk factor; statistics and numerical data; tetrahydrocannabinol; threshold limit value; threshold model; unclassified drug; unclassified enzyme; vitamin D deficiency

Physiological responses related to increased grain yield under drought in the first biotechnology‐derived drought‐tolerant maize - Nemali, Krishna S; Bonin, Christopher P; Dohleman, Frank G; Stephens, Mike; Reeves, William; Nelson, Donald E; Castiglioni, Paolo; Whitsel, Joy; Sammons, Bernard; Silady, Rebecca A; Anstrom, Donald; Sharp, Robert E; et al. (Plant Cell and Environment, 2015)
Maize (Zea mays ssp. mays L.) is highly susceptible to drought stress. This work focused on whole-plant physiological mechanisms by which a biotechnology-derived maize event expressing bacterial cold shock protein B (CspB), MON 87460, increased grain yield under drought. Plants of MON 87460 and a conventional control (hereafter 'control') were tested in the field under well-watered (WW) and water-limited (WL) treatments imposed during mid-vegetative to mid-reproductive stages during 2009-2011. Across years, average grain yield increased by 6% in MON 87460 compared with control under WL conditions. This was associated with higher soil water content at 0.5 m depth during the treatment phase, increased ear growth, decreased leaf area, leaf dry weight and sap flow rate during silking, increased kernel number and harvest index in MON 87460 than the control. No consistent differences were observed under WW conditions. This indicates that MON 87460 acclimated better under WL conditions than the control by lowering leaf growth which decreased water use during silking, thereby eliciting lower stress under WL conditions. These physiological responses in MON 87460 under WL conditions resulted in increased ear growth during silking, which subsequently increased the kernel number, harvest index and grain yield compared to the control. Copyright © 2014 The Authors. Plant, Cell & Environment published by John Wiley & Sons Ltd.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-772-605-388-897 tex.type: [object Object]
Keywords: *Biotechnology/mt [Methods]; *Droughts; *Zea mays/ph [Physiology]; Bacteria (microorganisms); Bacterial Proteins; Bacterial Proteins/ge [Genetics]; Biotechnology; CspB; Droughts; Ear; Edible Grain; Harvest index; Leaf area; Plant Leaves; Plant Leaves/ph [Physiology]; Plants; Genetically Modified; Plants; Genetically Modified/ph [Physiology]; Sap flow; Soil; Soil water content; Soil/ch [Chemistry]; Water use; Yield; Zea mays; acclimation; adaptation; bacterial protein; biotechnology; chemistry; cold-shock protein CspB; Bacteria; crop yield; dept.bio; drought; drought stress; food grain; genetics; index method; leaf area; maize; physiological response; physiology; plant leaf; procedures; protein; sap flow; soil; soil water; tolerance; transgenic plant; water use efficiency

Anti-inflammatory/antioxidant use in long-term maintenance cancer therapy: a new therapeutic approach to disease progression and recurrence. - Crawford, Sarah (Therapeutic advances in medical oncology, 2014)
The chronic, progressive clinical characteristics of many adult solid tumor malignancies suggest that a more effective therapeutic approach to cancer management may require long-term intervention using nontoxic systemic agents that block critical components of abnormal tumor physiology. Two highly promising systemic targets common to the development, progression and recurrence of many common cancers are dysregulated inflammatory and oxidation/reduction (redox) pathways. Compelling clinical data support the use of anti-inflammatory and antioxidant agents as a therapeutic modality for long-term use in patients diagnosed with several common cancers, including colon cancer and breast cancer. The therapeutic paradigm presented in this paper is the product of a synthesis of what is currently understood about the biological effects of inflammation and oxidative stress that contribute to tumorigenesis, disease progression and recurrence as well as results obtained from research on the use of prophylactics with anti-inflammatory or antioxidant properties in cancer prevention and treatment.
51 citations (Crossref) [2023-10-31] Place: England Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, New Haven, CT 06515, USA.
Keywords: anti-inflammatory agents; antiinflammatory agent; antioxidant; antioxidants; axitinib; bevacizumab; bosutinib; breast cancer; cabozantinib; cancer epidemiology; cancer growth; cancer recurrence; cancer therapy; cetuximab; chemoprophylaxis; chemotherapy; colon cancer; crizotinib; dasatinib; dept.bio; erlotinib; everolimus; gefitinib; human; imatinib; inflammation; ipilimumab; lapatinib; long term care; long-term maintenance cancer therapy; meta analysis (topic); nilotinib; nonhuman; oxidative stress; panitumumab; pazopanib; ponatinib; priority journal; randomized controlled trial (topic); reactive oxygen metabolite; regorafenib; review; ruxolitinib; sorafenib; sunitinib; systematic review (topic); temsirolimus; tofacitinib; trastuzumab; trastuzumab emtansine; unindexed drug; vandetanib; vemurafenib

Cluster M mycobacteriophages Bongo, PegLeg, and Rey with unusually large repertoires of tRNA isotypes - Pope, Welkin H; Anders, Kirk R; Baird, Madison A; Bowman, Charles A; Boyle, Michelle M; Broussard, Gregory W; Chow, Tiffany W; Clase, Kari; Cooper, Shannon D; Cornely, Kathleen; Dejong, Randall J; Delesalle, Veronique A; et al. (Journal of Virology, 2014)
Genomic analysis of a large set of phages infecting the common host Mycobacterium smegmatis mc2155 shows that they span considerable genetic diversity. There are more than 20 distinct types that lack nucleotide similarity with each other, and there is considerable diversity within most of the groups. Three newly isolated temperate mycobacteriophages, Bongo, PegLeg, and Rey, constitute a new group (cluster M), with the closely related phages Bongo and PegLeg forming subcluster M1 and the more distantly related Rey forming subcluster M2. The clusterMmycobacteriophages have siphoviral morphologies with unusually long tails, are homoimmune, and have larger than average genomes (80.2 to 83.7 kbp). They exhibit a variety of features not previously described in other mycobacteriophages, including noncanonical genome architectures and several unusual sets of conserved repeated sequences suggesting novel regulatory systems for both transcription and translation. In addition to containing transfer-messenger RNA and RtcB-like RNA ligase genes, their genomes encode 21 to 24 tRNA genes encompassing complete or nearly complete sets of isotypes. We predict that these tRNAs are used in late lytic growth, likely compensating for the degradation or inadequacy of host tRNAs. They may represent a complete set of tRNAs necessary for late lytic growth, especially when taken together with the apparent lack of codons in the same late genes that correspond to tRNAs that the genomes of the phages do not obviously encode. © 2014, American Society for Microbiology.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-261-678-659-153 tex.type: [object Object]
Keywords: Base Composition; Base Sequence; Codon; Conserved Sequence; DNA binding motif; DNA sequence; Gene Order; Genome Size; Genome; Viral; Inverted Repeat Sequences; Lysogeny; Multigene Family; Mycobacteriophages; Mycobacterium smegmatis; Open Reading Frames; Phylogeny; RNA cleavage; RNA degradation; RNA translation; RNA; Transfer; RNA; Viral; Repetitive Sequences; Nucleic Acid; Sequence Alignment; Virion; Virus Assembly; article; controlled study; dept.bio; gene cassette; gene control; gene structure; genetic analysis; genetic transcription; genetic variability; membrane protein; mycobacteriophage; mycobacteriophage Bongo; mycobacteriophage M; mycobacteriophage Pegleg; mycobacteriophage Rey; nonhuman; nucleotide sequence; priority journal; protein gp19; protein gp23; protein gp24; protein gp26; protein gp30; protein gp31; protein gp39; single stranded DNA binding protein; tmp gene; transfer RNA; unclassified drug; viral genetics; virus assembly; virus classification; virus immunity; virus morphology

Postcranial skeleton of Postosuchus kirkpatricki (Archosauria: Paracrocodylomorpha), from the upper Triassic of the United States - Weinbaum, Jonathan C (Geological Society, London, Special Publications, 2013)
Postosuchus kirkpatricki is a Late Triassic (Norian) 'rauisuchid' archosaur from North America. The initial description of the Postosuchus type material included elements from two poposaurids. This confusion has prevented adequate description of the material. Recent examination of the type material and other specimens of Postosuchus, and of related taxa, has helped clarify the osteology of Postosuchus. The type specimens represent c. 75% of the skeleton. Together with other referred material, Postosuchus remains one of the most completely known rauisuchids. The paratype skeleton, which is relatively complete, would have been c. 3.5-4 m in length, and the holotype would have been closer to 5-6 m. Analysis of the postcranial skeleton of Postosuchus suggests that it may have been an obligate biped (based in part on limb proportions, which are similar to some theropod dinosaurs, the size of the manus (30% of the size of the pes) and the highly reduced nature of the digits and vertebral measurements). Possible postcranial autapomorphies of Postosuchus include a large, rugose triangular supra-acetabular buttress confluent with the dorsal margin of the iliac blade, and a symmetrical pes with digits two and three being roughly equal in length. © The Geological Society of London 2013.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-386-820-858-734 tex.type: [object Object]
Keywords: Triassic; United States; dept.bio; osteology; peer-reviewed; reptile; skeleton; taxonomy; type specimen

A taxonomic and biostratigraphic re-evaluation of the Post Quarry vertebrate assemblage from the Cooper Canyon Formation (Dockum Group, Upper Triassic) of southern Garza County, western Texas - Martz, Jeffrey W.; Mueller, Bill D.; Nesbitt, Sterling J.; Stocker, Michelle R.; Parker, William G.; Atanassov, Momchil N.; Fraser, Nicholas C.; Weinbaum, Johnathan; Lehane, James R. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
The Post Quarry, within the lower part of the type section of the Upper Triassic Cooper Canyon Formation in southern Garza County, western Texas, contains a remarkably diverse vertebrate assemblage. The Post Quarry has produced: the small temnospondyl Rileymillerus cosgriffi; the metoposaurid Apachesaurus gregorii; possible dicynodonts and eucynodonts; a clevosaurid sphenodontian; non-archosauriform archosauromorphs (Trilophosaurus dornorum, simiosaurians, and possibly Malerisaurus); the phytosaur Leptosuchus; several aetosaurs (Calyptosuchus wellesi, Typothorax coccinarum, Paratypothorax, and Desmatosuchus smalli); the poposauroid Shuvosaurus inexpectatus (Chatterjeea elegans); the rauisuchid Postosuchus kirkpatricki; an early crocodylomorph; several dinosauromorphs (the lagerpetid Dromomeron gregorii, the silesaurid Technosaurus smalli, a herrerasaurid, and an early neotheropod); and several enigmatic small diapsids. Revised lithostratigraphic correlations of the lower Cooper Canyon Formation with the Tecovas Formation, the occurrence of Leptosuchus, and the overall composition of the assemblage indicate that the Post Quarry falls within the Adamanian biozone, and not the Revueltian biozone. Stratigraphic subdivision of the Adamanian biozone may be possible, and the Post Quarry may be correlative with the upper part of the Adamanian biozone in Arizona. The age of the Post Quarry assemblage is possibly late Lacian or earliest Alaunian (late early Norian or earliest middle Norian), between 220 and 215 Ma. © 2013 The Royal Society of Edinburgh.
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00103 tex.type: [object Object]
Keywords: Adamanian biozone; Dinosauromorpha; Garza County; Leptosuchus; Pseudosuchia; Texas; Triassic; United States; biostratigraphy; biozonation; dept.bio; faunal diversity; fossil assemblage; land vertebrate faunachrons; stratigraphic correlation; taxonomy; type locality; vertebrate; vertebrate locality

A survey of skeletal elements in the orbit of Pseudosuchia and the origin of the crocodylian palpebral - Nesbitt, Sterling J.; Turner, Alan H.; Weinbaum, Jonathan C. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
14 citations (Crossref) [2023-10-31] Citation Key Alias: pop00106 tex.type: [object Object]
Keywords: Aetosaurus ferratus; Archosauria; Crocodylomorpha; Postosuchus kirkpatricki; Saurosuchus galilei; crocodilian; dept.bio; evolution; extinction; fossil assemblage; novelty; skeletal remains; supraorbital; taxonomy

The long journey of stem cell therapeutics. - Crawford, Sarah (Genome Medicine, 2012)
A report on the Euroepistem 2011 meeting 'Epigenomic Programming and Stem Cells for Drug Discovery', Paris, France, 21-22 November 2011.
0 citations (Crossref) [2023-10-31] Place: England Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. crawfords2@southernct.edu.
Keywords: Article; dept.bio; embryonic stem cell; epigenetics; gene; gene silencing; human; induced pluripotent stem cell; nonhuman; priority journal; stem cell transplantation; transcription regulation

A new species of Acentrella Bengtsson (Ephemeroptera: Baetidae) from New York and New England (USA), redescription of the nymph of A. parvula (McDunnough), and key to known adult males of Nearctic Acentrella - Burian, Steven K; Myers, Luke W (Aquatic Insects, 2011)
A new species Acentrella rallatoma (type locality: Connetquot River, Oakdale, NY, USA) is described from nymphs and reared adults. Additional specimens were studied from southeastern New York, southeastern New Hampshire, coastal Connecticut, and Martha's Vineyard, MA, USA. Nymphs can be separated from those of other Nearctic species by: scraper-like outer incisors of mandibles, cerci alternately banded from bases to tips, and row of robust bristle-like setae (with modified tips) on dorsal edge of femora. Male imagos can be separated from those that lack hind wings by: distinctive colour pattern of abdominal terga, and genitalia with pigmented sclerotised penes cover. Comparative analysis of A. rallatoma with other Nearctic species revealed a lack of comparative data on nymphs of its presumptive sister species A. parvula. To facilitate future studies of this group, the nymph of A. parvula is redescribed and regional differences are discussed. Abdominal colour patterns of A. parvula that vary over its range from Florida, USA to Labrador, Canada are illustrated. Problems concerning genus-level diagnostic characters for Acentrella nymphs and adults are discussed to facilitate placement of future taxa. To complement existing keys to Nearctic nymphs of Acentrella a provisional key to the known adult males is given. © 2011 Copyright Taylor and Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-428-772-783-321 tex.type: [object Object]
Keywords: A. parvula; Acentrella; Acentrella parvula; Baetidae; Ephemeroptera; dept.bio; new species

Effect of increased extracellular Ca++ on microvesicle production and tumor spheroid formation - Crawford, Sarah; Diamond, Deanna; Brustolon, Laura; Penarreta, Rafaela (Cancer microenvironment : official journal of the International Cancer Microenvironment Society, 2011)
Research on the composition of the tumor micro-environment has demonstrated that membrane delimited microvesicles are shed from many types of malignant tumors, in the peripheral blood of cancer patients as well as in culture media of tumor cells propagated in vitro (Ginestra et al. Anticancer Res 18:3433-3437, 1998). Their documented effects involve the activation of signal transduction pathways by cellular cross-talk that are associated with epigenetic mechanisms that may be important in tumor progression, metastasis, and the activation of angiogenesis (Distler et al. Arthritis Rheum 52:3337-3348, 2005). Live cell imaging microscopic studies conducted in our laboratory of the formation of solid tumor spheroids in vitro show that the shedding of microvesicular structures from tumor cells occurs during this process. The observed properties of the tumor microvesicles suggest a role in solid tumor formation and intercellular communication. The tumor associated microvesicles were shown to be non-apoptotic based on the absence of fluorescent nuclear staining by acridine orange/ethidium bromide staining. Increased concentration of extracellular Ca(++) [5-20 mM] resulted in an increase in the production of tumor-derived microvesicles and also to result in the formation of tumor spheroids whose size was considerably smaller than controls. Increased extracellular [Ca(++)] was also observed to induce the rapid dissociation of solid tumor spheroids to smaller cell aggregates in the absence of significant apoptosis.
19 citations (Crossref) [2023-10-31] Place: Netherlands Crawford, Sarah. Cancer Biology Research Laboratory, Biology Department, Southern Connecticut State University, Jennings Hall 219, 501 Crescent Street, New Haven, CT 06515 USA.
Keywords: Extracellular Ca++; Live cell imaging; Multicellular tumor spheroid; Tumor associated microvesicle; acridine orange; angiogenesis; apoptosis; article; breast carcinoma; calcium ion; cancer cell culture; cell aggregation; cell nucleus; concentration (parameters); controlled study; cytochemistry; dept.bio; epigenetics; ethidium bromide; extracellular calcium; glioblastoma; human; human cell; in vitro study; membrane vesicle; metastasis potential; microscopy; molecular interaction; osteosarcoma; priority journal; signal transduction; tumor growth; tumor microenvironment; tumor spheroid; tumor vascularization

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
157 citations (Crossref) [2023-10-31] tex.ids: ISI:000279276600002, Rogers2010, lens.org/048-194-199-785-52X tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

The ratio of gametophytes to tetrasporophytes of intertidal chondrus crispus (gigartinaceae) across a salinity gradient - Guidone, Michele; Grace, Sean (Rhodora, 2010)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-225-776-360-25X tex.type: [object Object]
Keywords: Chondrus; Chondrus crispus; Gigartinaceae; dept.bio

Reproductive behavior in horseshoe crabs: Does density matter? - Mattei, Jennifer; Beekey, Mark A; Rudman, Adam; Woronik, Alyssa (Current Zoology, 2010)
While the four species of horseshoe crabs share many common reproductive traits with respect to their reproductive systems, they do differ with respect to their mating behavior (monogamy vs. polygynandry). Past research has attributed these differences to a number of factors including: spawning densities, operational sex ratios (OSR's), male condition (or age), environmental and/or genetic factors, or a combination thereof. Mating behaviors in the three Asian horseshoe crab species (Tachypleus gigas, T. tridentatus, and Carcinoscorpius rotundicauda) with low spawning densities and 1:1 operational sex ratios are typically monogamous. In Limulus polyphemus, mating behavior is more variable ranging from monogamy to polygynandry. Here we provide evidence, through a long term behavioral study, that variation in mating behavior is influenced by population density in L. polyphemus. Our study population on two beaches in Connecticut (Long Island Sound) have a spawning density 400 times less than that found in Delaware Bay (0.002 females/m2 vs. 0.8 females/m2) but similar operational sex ratios. Between 90%-95% of all spawning females in CT were paired with only one male, thus exhibiting monogamous behavior. In contrast, between 30 and 60% of spawning females in Delaware Bay have more than one mate and produce clutches of eggs with multiple paternities. Male condition played no role in mating behavior in CT populations. We also observed that on average 18% of the females on the spawning beaches are single. These results suggest that population density is an important condition that determines mating behavior. Also, low population density may lead to decreased mate finding ability and lost opportunities for spawning [Current Zoology 56 (5): 634-642, 2010]. © 2010 Current Zoology.
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-298-586-515-449 tex.type: [object Object]
Keywords: Carcinoscorpius rotundicauda; Limulus; Limulus polyphemus; Mating behavior; Merostomata; Monogamy; Polygynandry; Population density; Tachypleus gigas; dept.bio

Biotechnological potential of aquatic plant-microbe interactions. - Stout, L; Nusslein, K (Current opinion in biotechnology, 2010)
The rhizosphere in terrestrial systems is the region of soil surrounding plant roots where there is increased microbial activity; in aquatic plants, this definition may be less clear because of diffusion of nutrients in water, but there is still a zone of influence by plant roots in this environment [1]. Within that zone chemical conditions differ from those of the surrounding environment as a consequence of a range of processes that were induced either directly by the activity of plant roots or by the activity of rhizosphere microflora. Recently, there are a number of new studies related to rhizospheres of aquatic plants and specifically their increased potential for remediation of contaminants, especially remediation of metals through aquatic plant-microbial interaction. Copyright 2010 Elsevier Ltd. All rights reserved.
44 citations (Crossref) [2023-10-31] Place: England Stout, L. Department of Biology, Southern Connecticut State University, New Haven, CT 06515, United States. stoutl1@southernct.edu
Keywords: *Biotechnology/mt [Methods]; *Plants/mi [Microbiology]; 1 aminocyclopropanecarboxylic acid; Aquaculture; Aquatic plants; Biodegradation; Environmental; Biotechnology; Chemical conditions; Hydrogen-Ion Concentration; Microbial activities; Microbial interactions; Microflora; New study; Plant Roots; Plant Roots/mi [Microbiology]; Plant roots; Plants; Pollution; Rhizobium leguminosarum; Soils; Surrounding environment; Terrestrial systems; Zone of influences; adenosine triphosphatase; aquatic environment; aquatic flora; bacterial strain; biofilm; biofiltration; biotechnological procedures; biotechnology; cadmium; chromium; cobalt; copper; dept.bio; environmental exposure; heavy metal removal; homeostasis; metallothionein; microorganism; nickel; nonhuman; pH; phytochelatin; phytoremediation; plant growth; plant microorganism interaction; priority journal; process technology; protein binding; protein synthesis; review; rhizofiltration; rhizosphere; siderophore; transgene; volatilization; zinc

The mid-network mayfly maxima (MMM): A general pattern of mayfly (Ephemeroptera) species richness within drainage networks and what we can learn from it - Burian, Steven K. (Zoosymposia, 2019)
For the last 93 years mayfly diversity has been studied at all taxonomic levels from families to populations and all spatial and temporal scales. This has resulted in the description of almost every possible pattern with regard to latitude, elevation, habitat, climate, and season. However, if the focus is on species and sampling restricted to nymphs and the spatial scale limited to drainage networks, then a single recurring pattern appears—the hump-shaped Mid-network Mayfly Maxima (MMM). Past studies have attempted to explain this hump-shaped pattern with regards to some combination of ecologic, hydrologic, climatic, anthropogenic, or historic variables. There is wide agreement that some of these variables are important to the occurrence and distribution of individual species, but there is no consensus as to what combination of these variables comprises the best general explanation of the humped-shaped pattern. Because of the lack of agreement on how to explain this recurring pattern for mayflies and an unwillingness to acknowledge it as a general feature of drainage networks, where mayflies occur, we have become stuck trying to tease out a cause and have failed to recognize that although knowing a cause is important it may not be relevant to the broader use of this information for biomonitoring, climate monitoring, habitat management, and conservation now. I believe that there is sufficient evidence that the MMM exists and occurs in almost every major drainage system and is reasonably predictable using basic attributes of drainage networks pertinent to the aquatic life stage (nymphs). Herein I will summarize pertinent studies that support this contention; reexamine some results from one of the most comprehensive recent studies that included mayfly taxa along altitudinal gradients in North America by Gill et al. (2014), as well as a test dataset from a river in western Maine, USA; comment on information needed to estimate the location of MMM in any drainage network and how the MMM can be used; and discuss how the extent of common vs. rare species affect the perceptions of the regional species pool and the MMM.
Number: 1
Keywords: Ephemeroptera; Mayfly; dept.bio; peer-reviewed; ⚠️ Invalid DOI

So You Want to Start an Institutional Biosafety Committee - Schniederberend, Maren; Fontes, Benjamin; Jeffrey, Rachel (Applied Biosafety, 2019)
Introduction: The number of institutions engaging in research with potentially biohazardous materials has increased, indicating a need for newly formed Institutional Biosafety Committees (IBCs) in the United States and for similar biorisk management committees located outside the United States. Our institution identified the need for an IBC due to the growth of pertinent activities on campus. Objectives: This article shares our experiences creating a new IBC at our institution from September 2017 to April 2019. Our lessons learned and approaches to the challenges faced may be helpful to others finding themselves with similar needs. Methods: In this case study, we outline IBC membership, documents, relationships with federal agencies and within the institution, creation of registration forms, and the review process. Along with our account, we have included links to helpful resources from federal agencies. Results: At the time of the submission of this article, we have established our IBC and reviewed two registrations. Conclusion: This case report demonstrates the successful creation of an IBC that works for our current institutional needs. © ABSA International 2019.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/177-624-967-404-713, pop00102 tex.type: [object Object]
Keywords: BMBL; EHS; IBC; NIH Guidelines; biorisk management; dept.bio; peer-reviewed; standard operating procedure

Ephemeroptera - Burian, Steven K. (An introduction to the aquatic insects of North America, 2019)
"As with previous editions, this new one is intended to serve as a standard guide to the aquatic and semiaquatic insects of North America"–Preface, xi.
Google-Books-ID: nLh_yAEACAAJ
Keywords: dept.bio; faculty_collection

Understanding maladaptation by uniting ecological and evolutionary perspectives - Brady, Steven P.; Bolnick, Daniel I.; Barrett, Rowan D. H.; Chapman, Lauren; Crispo, Erika; Derry, Alison M.; Eckert, Christopher G.; Fraser, Dylan J.; Fussmann, Gregor F.; Gonzalez, Andrew; Guichard, Frederic; Lamy, Thomas; et al. (The American Naturalist, 2019)
Evolutionary biologists have long trained their sights on adaptation, focusing on the power of natural selection to produce relative fitness advantages while often ignoring changes in absolute fitness. Ecologists generally have taken a different tack, focusing on changes in abundance and ranges that reflect absolute fitness while often ignoring relative fitness. Uniting these perspectives, we articulate various causes of relative and absolute maladaptation and review numerous examples of their occurrence. This review indicates that maladaptation is reasonably common from both perspectives, yet often in contrasting ways. That is, maladaptation can appear strong from a relative fitness perspective, yet populations can be growing in abundance. Conversely, resident individuals can appear locally adapted (relative to nonresident individuals) yet be declining in abundance. Understanding and interpreting these disconnects between relative and absolute maladaptation, as well as the cases of agreement, is increasingly critical in the face of accelerating human-mediated environmental change. We therefore present a framework for studying maladaptation, focusing in particular on the relationship between absolute and relative fitness, thereby drawing together evolutionary and ecological perspectives. The unification of these ecological and evolutionary perspectives has the potential to bring together previously disjunct research areas while addressing key conceptual issues and specific practical problems. © 2019 by The University of Chicago. All rights reserved.
54 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Fitness; Global change; Maladaptation; adult; article; dept.bio; drawing; ecologist; environmental change; female; global change; human; human experiment; male; natural selection; peer-reviewed; resident

Causes of maladaptation. - Brady, Steven P; Bolnick, Daniel I; Angert, Amy L; Gonzalez, Andrew; Barrett, Rowan D H; Crispo, Erika; Derry, Alison M; Eckert, Christopher G; Fraser, Dylan J; Fussmann, Gregor F; Guichard, Frederic; Lamy, Thomas; et al. (Evolutionary applications, 2019)
Evolutionary biologists tend to approach the study of the natural world within a framework of adaptation, inspired perhaps by the power of natural selection to produce fitness advantages that drive population persistence and biological diversity. In contrast, evolution has rarely been studied through the lens of adaptation's complement, maladaptation. This contrast is surprising because maladaptation is a prevalent feature of evolution: population trait values are rarely distributed optimally; local populations often have lower fitness than imported ones; populations decline; and local and global extinctions are common. Yet we lack a general framework for understanding maladaptation; for instance in terms of distribution, severity, and dynamics. Similar uncertainties apply to the causes of maladaptation. We suggest that incorporating maladaptation-based perspectives into evolutionary biology would facilitate better understanding of the natural world. Approaches within a maladaptation framework might be especially profitable in applied evolution contexts - where reductions in fitness are common. Toward advancing a more balanced study of evolution, here we present a conceptual framework describing causes of maladaptation. As the introductory article for a Special Feature on maladaptation, we also summarize the studies in this Issue, highlighting the causes of maladaptation in each study. We hope that our framework and the papers in this Special Issue will help catalyze the study of maladaptation in applied evolution, supporting greater understanding of evolutionary dynamics in our rapidly changing world.
79 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Bolnick, Daniel I. Department of Ecology and Evolutionary Biology University of Connecticut Mansfield CT USA. Angert, Amy L. Departments of Botany and Zoology University of British Columbia Vancouver BC Canada. Gonzalez, Andrew. Department of Biology McGill University Montreal QC Canada. Gonzalez, Andrew. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Department of Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Redpath Museum McGill University Montreal QC Canada. Crispo, Erika. Department of Biology Pace University New York NY USA. Derry, Alison M. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Derry, Alison M. Departement des sciences biologiques Universite du Quebec a Montreal Montreal QC Canada. Eckert, Christopher G. Department of Biology Queen's University Kingston ON Canada. Fraser, Dylan J. Department of Biology Concordia University Montreal QC Canada. Fussmann, Gregor F. Department of Biology McGill University Montreal QC Canada. Fussmann, Gregor F. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Guichard, Frederic. Department of Biology McGill University Montreal QC Canada. Guichard, Frederic. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Lamy, Thomas. Departement de sciences biologiques Universite de Montreal Montreal QC Canada. Lamy, Thomas. Marine Science Institute University of California Santa Barbara CA USA. McAdam, Andrew G. Department of Integrative Biology University of Guelph Guelph ON Canada. Newman, Amy E M. Department of Integrative Biology University of Guelph Guelph ON Canada. Paccard, Antoine. McGill University Genome Center Montreal QC Canada. Rolshausen, Gregor. Senckenberg Biodiversity and Climate Research Centre (SBiK-F) Frankfurt am Main Germany. Simons, Andrew M. Department of Biology Carleton University Ottawa ON Canada. Hendry, Andrew P. Department of Biology McGill University Montreal QC Canada. Hendry, Andrew P. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Hendry, Andrew P. Redpath Museum McGill University Montreal QC Canada.
Keywords: adaptation; dept.bio; fitness; global change; maladaptation; peer-reviewed

Fundamental and applied pursuits in evolutionary toxicology are mutually beneficial: A reply to Hahn (2018). - Brady, Steven P; Monosson, Emily; Matson, Cole; Bickham, John W (Evolutionary applications, 2019)
0 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. Ronin Institute for Independent Scholars, Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station TX USA.
Keywords: Evolutionary toxicology; contemporary evolution; dept.bio; ecotoxicology; peer-reviewed

Fitter frogs from polluted ponds: The complex impacts of human-altered environments - Brady, Steven P.; Zamora‐Camacho, Francisco J.; Eriksson, Fredrik A. A.; Goedert, Debora; Comas, Mar; Calsbeek, Ryan (Evolutionary Applications, 2019)
Human-modified habitats rarely yield outcomes that are aligned with conservation ideals. Landscapes that are subdivided by roads are no exception, precipitating negative impacts on populations due to fragmentation, pollution, and road kill. Although many populations in human-modified habitats show evidence for local adaptation, rarely does environmental change yield outright benefits for populations of conservation interest. Contrary to expectations, we report surprising benefits experienced by amphibian populations breeding and dwelling in proximity to roads. We show that roadside populations of the wood frog, Rana sylvatica, exhibit better locomotor performance and higher measures of traits related to fitness compared with frogs from less disturbed environments located further away from roads. These results contrast previous evidence for maladaptation in roadside populations of wood frogs studied elsewhere. Our results indicate that altered habitats might not be unequivocally detrimental and at times might contribute to metapopulation success. While the frequency of such beneficial outcomes remains unknown, their occurrence underscores the complexity of inferring consequences of environmental change.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-521-919-587-494, pop00127 tex.type: [object Object]
Keywords: amphibian; dept.bio; human-modified habitats; maladaptation; peer-reviewed; road salt; roads

Immunofluorescence and image analysis pipeline for Drosophila motor neurons - Brown, Jeremy R; Brown, Jeremy R; Phongthachit, Chanpasith; Sulkowski, Mikolaj J (Biology Methods and Protocols, 2019)
The neuromuscular junction (NMJ) of larval Drosophila is widely used as a genetic model for basic neuroscience research. The presynaptic side of the NMJ is formed by axon terminals of motor neurons, the soma of which reside in the ventral ganglion of the central nervous system (CNS). Here we describe a streamlined protocol for dissection and immunostaining of the Drosophila CNS and NMJ that allows processing of multiple genotypes within a single staining tube. We also present a computer script called Automated Image Analysis with Background Subtraction which facilitates identification of motor nuclei, quantification of pixel intensity, and background subtraction. Together, these techniques provide a pipeline for neuroscientists to compare levels of different biomolecules in motor nuclei. We conclude that these methods should be adaptable to a variety of different cell and tissue types for the improvement of efficiency, reproducibility, and throughput during data quantification. © 2019 The Author(s) 2019. Published by Oxford University Press.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-055-143-711-580 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Is it time to begin prenatal/neonatal screening for autism risk? - Crawford, Sarah Adelaide (Global Journal of Pediatrics & Neonatal Care, 2019)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-162-730-836-405, pop00188
Keywords: dept.bio; peer-reviewed

Conservation through the lens of (mal)adaptation: Concepts and meta-analysis - Derry, Alison Margaret; Fraser, Dylan J.; Brady, Steven P.; Astorg, Louis; Lawrence, Elizabeth R.; Martin, Gillian K.; Matte, Jean-Michel; Dastis, Jorge Octavio Negrín; Paccard, Antoine; Barrett, Rowan D. H.; Chapman, Lauren J.; Lane, Jeffrey E.; et al. (Evolutionary Applications, 2019)
Evolutionary approaches are gaining popularity in conservation science, with diverse strategies applied in efforts to support adaptive population outcomes. Yet conservation strategies differ in the type of adaptive outcomes they promote as conservation goals. For instance, strategies based on genetic or demographic rescue implicitly target adaptive population states whereas strategies utilizing transgenerational plasticity or evolutionary rescue implicitly target adaptive processes. These two goals are somewhat polar: adaptive state strategies optimize current population fitness, which should reduce phenotypic and/or genetic variance, reducing adaptability in changing or uncertain environments; adaptive process strategies increase genetic variance, causing maladaptation in the short term, but increase adaptability over the long term. Maladaptation refers to suboptimal population fitness, adaptation refers to optimal population fitness, and (mal)adaptation refers to the continuum of fitness variation from maladaptation to adaptation. Here, we present a conceptual classification for conservation that implicitly considers (mal)adaptation in the short-term and long-term outcomes of conservation strategies. We describe cases of how (mal)adaptation is implicated in traditional conservation strategies, as well as strategies that have potential as a conservation tool but are relatively underutilized. We use a meta-analysis of a small number of available studies to evaluate whether the different conservation strategies employed are better suited toward increasing population fitness across multiple generations. We found weakly increasing adaptation over time for transgenerational plasticity, genetic rescue, and evolutionary rescue. Demographic rescue was generally maladaptive, both immediately after conservation intervention and after several generations. Interspecific hybridization was adaptive only in the F1 generation, but then rapidly leads to maladaptation. Management decisions that are made to support the process of adaptation must adequately account for (mal)adaptation as a potential outcome and even as a tool to bolster adaptive capacity to changing conditions.
41 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-301-824-151-444, pop00098 tex.type: [object Object]
Keywords: adaptation; demographic rescue; dept.bio; evolutionary rescue; gene flow; genetic rescue; hybridization; peer-reviewed; transgenerational plasticity; translocation

Ecological feedbacks stabilize a turf-dominated ecosystem at the southern extent of kelp forests in the Northwest Atlantic. - Feehan, Colette J; Grace, Sean P; Narvaez, Carla A (Scientific reports, 2019)
Temperate marine ecosystems globally are undergoing regime shifts from dominance by habitat-forming kelps to dominance by opportunistic algal turfs. While the environmental drivers of shifts to turf are generally well-documented, the feedback mechanisms that stabilize novel turf-dominated ecosystems remain poorly resolved. Here, we document a decline of kelp Saccharina latissima between 1980 and 2018 at sites at the southernmost extent of kelp forests in the Northwest Atlantic and their replacement by algal turf. We examined the drivers of a shift to turf and feedback mechanisms that stabilize turf reefs. Kelp replacement by turf was linked to a significant multi-decadal increase in sea temperature above an upper thermal threshold for kelp survival. In the turf-dominated ecosystem, 45% of S. latissima were attached to algal turf rather than rocky substrate due to preemption of space. Turf-attached kelp required significantly (2 to 4 times) less force to detach from the substrate, with an attendant pattern of lower survival following 2 major wave events as compared to rock-attached kelp. Turf-attached kelp allocated a significantly greater percentage of their biomass to the anchoring structure (holdfast), with a consequent energetic trade-off of slower growth. The results indicate a shift in community dominance from kelp to turf driven by thermal stress and stabilized by ecological feedbacks of lower survival and slower growth of kelp recruited to turf.
24 citations (Crossref) [2023-10-31] Place: England Feehan, Colette J. Department of Biology, Montclair State University, Montclair, NJ, 07043, USA. feehanc@montclair.edu. Grace, Sean P. Department of Biology and Werth Center for Coastal and Marine Studies, Southern Connecticut State University, New Haven, CT, 06515, USA. Narvaez, Carla A. Department of Biology, Villanova University, Villanova, PA, 19085, USA.
Keywords: *Forests; *Kelp/ph [Physiology]; *Marine Biology/mt [Methods]; *Seawater; Atlantic Ocean; Bays; Biomass; Climate Change; Forests; Kelp; Kelp/gd [Growth & Development]; Marine Biology; Rhode Island; Seasons; Seawater; Temperature; article; bay; biomass; climate change; dept.bio; driver; feedback system; forest; growth; development and aging; human; kelp; marine biology; physiology; procedures; sea water; season; temperature; temperature stress

Fitness attributes of bacterial and fungal seed endophytes of tall fescue - Roberts, Elizabeth Lewis; Mormile, Brendan; Adamchek, Christopher (Seed Endophytes: Biology and Biotechnology, 2019)
Increased fitness in tall fescue (Festuca arundinacea) is attributed to infection by Epichloë coenophiala. However, plant growth-promoting (PGP) bacteria also increase the fitness of many host plants, and PGP bacteria have been shown to dominate the phyllosphere and rhizosphere microbiome of E. coenophiala-infected (E+) tall fescue. Because E. coenophialum lives endophytically in tall fescue seeds, we hypothesized that PGP bacteria also live within the seeds and could provide fitness advantages to the host. Endophyte-infected (E+) and endophyte-free (E−) Kentucky-31 tall fescue seeds were surface sterilized to remove epiphytic bacteria. Surface sterilized and non-surface sterilized control plants of each type were cultivated for 6 weeks before withholding water to simulate drought. Normal watering was resumed after 4 days. Plant recovery of each group was measured by assigning a numerical value to tillers based on the state of decline. Surface-sterilized E+ plants were unable to recover as efficiently as E+ controls but outperformed both E− groups. Additionally, total 16S amplified DNA extracted from each seed type was analyzed with Illumina sequencing to assess the internal microbial communities from E+ and E− seeds as well as the seed coat microbiome. E+ seeds have lower diversity of endophytic bacterial species and are dominated by Pseudomonadaceae. Further, several of the seed endophytes are PGP bacterial strains.
Citation Key Alias: lens.org/004-523-831-959-190
Keywords: Clavicipitaceae; Epichloë coenophialum; Epichloë spp.; Plant growth promotion; Plant growth-promoting bacteria; Plant growthpromoting bacteria; Stress tolerance; Tall fescue; dept.bio

Colonization of the tsetse fly midgut with commensal Kosakonia cowanii Zambiae inhibits trypanosome infection establishment. - Weiss, Brian L; Maltz, Michele A; Vigneron, Aurelien; Wu, Yineng; Walter, Katharine S; O'Neill, Michelle B; Wang, Jingwen; Aksoy, Serap (PLOS Pathogens, 2019)
Tsetse flies (Glossina spp.) vector pathogenic trypanosomes (Trypanosoma spp.) in sub-Saharan Africa. These parasites cause human and animal African trypanosomiases, which are debilitating diseases that inflict an enormous socio-economic burden on inhabitants of endemic regions. Current disease control strategies rely primarily on treating infected animals and reducing tsetse population densities. However, relevant programs are costly, labor intensive and difficult to sustain. As such, novel strategies aimed at reducing tsetse vector competence require development. Herein we investigated whether Kosakonia cowanii Zambiae (Kco_Z), which confers Anopheles gambiae with resistance to Plasmodium, is able to colonize tsetse and induce a trypanosome refractory phenotype in the fly. Kco_Z established stable infections in tsetse's gut and exhibited no adverse effect on the fly's survival. Flies with established Kco_Z infections in their gut were significantly more refractory to infection with two distinct trypanosome species (T. congolense, 6% infection; T. brucei, 32% infection) than were age-matched flies that did not house the exogenous bacterium (T. congolense, 36% infected; T. brucei, 70% infected). Additionally, 52% of Kco_Z colonized tsetse survived infection with entomopathogenic Serratia marcescens, compared with only 9% of their wild-type counterparts. These parasite and pathogen refractory phenotypes result from the fact that Kco_Z acidifies tsetse's midgut environment, which inhibits trypanosome and Serratia growth and thus infection establishment. Finally, we determined that Kco_Z infection does not impact the fecundity of male or female tsetse, nor the ability of male flies to compete with their wild-type counterparts for mates. We propose that Kco_Z could be used as one component of an integrated strategy aimed at reducing the ability of tsetse to transmit pathogenic trypanosomes.
28 citations (Crossref) [2023-10-31] Place: United States Weiss, Brian L. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Maltz, Michele A. Southern Connecticut State University, New Haven, Connecticut, United States of America. Vigneron, Aurelien. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wu, Yineng. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Walter, Katharine S. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. O'Neill, Michelle B. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wang, Jingwen. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Aksoy, Serap. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Erratum in (EIN)
Keywords: *Trypanosoma brucei brucei/py [Pathogenicity]; *Trypanosoma congolense/py [Pathogenicity]; *Trypanosomiasis; African/pc [Prevention & Control]; *Tsetse Flies/mi [Microbiology]; *Tsetse Flies/ps [Parasitology]; Adult; Africa South of the Sahara; Africa south of the Sahara; African trypanosomiasis; Animals; Anopheles; Anopheles gambiae; Anopheles/mi [Microbiology]; Article; Drosophila; Enterobacteriaceae; Female; Glossinidae; Humans; Male; Mosquito Vectors; Mosquito Vectors/mi [Microbiology]; Mosquito Vectors/ps [Parasitology]; Plasmodium; Serratia infection; Symbiosis; Trypanosoma brucei brucei; Trypanosoma congolense; Trypanosomiasis; African; Trypanosomiasis; African/me [Metabolism]; Trypanosomiasis; African/mi [Microbiology]; Trypanosomiasis; African/ps [Parasitology]; Tsetse Flies; adult; animal; animal experiment; animal model; animal tissue; antibacterial activity; ascorbic acid; bacterial load; blood flow; cell proliferation assay; clinical effectiveness; colony forming unit; controlled study; cysteine; dept.bio; disease predisposition; economics; female; fitness; fluorescence; genotype phenotype correlation; health program; human; immune system; male; metabolism; microbial colonization; microbiology; microscopy; mosquito vector; nonhuman; pH; parasitology; pathogenicity; peer-reviewed; peptidoglycan recognition protein; population; probability; semen analysis; survival analysis; symbiosis; trypanosomiasis

Antibacterial Assessment of Heteroaryl, Vinyl, Benzyl, and Alkyl Tetrazole Compounds. - Dudley, Joshua; Feinn, Liana; DeFrancesco, Heather; Lindsay, Erica; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2018)
Background: In previous reports, the antibacterial properties of certain tetrazole derivatives have been described. We have previously reported the antibac...
6 citations (Crossref) [2023-10-31] Place: Netherlands Dudley, Joshua. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Feinn, Liana. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. DeFrancesco, Heather. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Lindsay, Erica. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Coca, Adiel. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Roberts, Elizabeth Lewis. Biology Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States.
Keywords: *Anti-Bacterial Agents/pd [Pharmacology]; *Tetrazoles/pd [Pharmacology]; 1 (1h tetrazol 5 yl)isoquinoline; 1; 2 di(1h tetrazol 5 yl)ethene; 2 (1h tetrazol 5 yl)pyrazine; 4 (1h tetrazol 5 yl)pyridine; 5 (1h pyrrol 2 yl) 1h tetrazole; 5 (2 methoxybenzyl) 1h tetrazole; 5 (furan 2 yl) 1h tetrazole; 5 (naphthalen 2 ylmethyl) 1h tetrazole; 5 (pyrrol 2 yl) 1h tetrazole; 5 (thiophen 3 yl) 1h tetrazole; 5 styryl 1h tetrazole; 5-substituted 1H-tetrazoles; (3 + 2) cycloaddition; Amoxicillin; Amoxicillin/pd [Pharmacology]; Anti-Bacterial Agents; Anti-Bacterial Agents/cs [Chemical Synthesis]; Antibacterial activity; Antimicrobial activity; Article; Cerium(III) chloride heptahydrate; Escherichia coli; Escherichia coli/de [Drug Effects]; Heterocycles; Microbial Sensitivity Tests; Microwave; Molecular Structure; Pseudomonas aeruginosa; Pseudomonas aeruginosa/de [Drug Effects]; Staphylococcus aureus; Staphylococcus aureus/de [Drug Effects]; Sulfamethoxazole; Sulfamethoxazole/pd [Pharmacology]; Tetrazoles; Tetrazoles/cs [Chemical Synthesis]; Trimethoprim; Trimethoprim/pd [Pharmacology]; amoxicillin; antibacterial activity; antibiotic agent; antiinfective agent; benzilic acid derivative; carbon nuclear magnetic resonance; chemical structure; controlled study; cotrimoxazole; dept.bio; dept.che; drug effect; heating; incubation time; microbial sensitivity test; minimum inhibitory concentration; nonhuman; peer-reviewed; phenyl(1h tetrazol 5 yl)methanol; priority journal; substitution reaction; sulfamethoxazole; synthesis; tetrazole derivative; trimethoprim; unclassified drug; vinyl derivative

The gene book: Explorations in the code of life - Crawford, Sarah Adelaide (Cognella Academic Publishing, 2018)
The Gene Book: Explorations in the Code of Life is designed to introduce undergraduate college students to foundational concepts in genetics. The text provides in-depth coverage of the essential principles of genetics, from Mendel to molecular gene therapy, and reads like a story, guiding readers through each of these areas in an interesting, engaging, and enlightening way. Milestone scientific discoveries introduce conceptual topics in each of the 10 chapters. The significance of each genetics paradigm is reinforced by the meaningful research context in which it is placed, whether the focus is single gene inheritance of disorders such as PKU and cystic fibrosis, or more complex genetic phenomena. Chromosomes, cell division, and cytogenetic disorders, including Down Syndrome and leukemia, are presented in a riveting historical context. In addition, the principles of molecular genetics are a major focus of this book. Students learn about the double helix, DNA replication, gene expression, mutation, natural selection, genomics, and the tools of molecular DNA analysis. Approachable and effective, The Gene Book is a highly readable comprehensive text on genetics principles designed to highlight essential concepts that make up their very core. The text is well suited to undergraduate genetics courses and can also be used as a primer for more advanced undergraduate and graduate courses in medial or molecular genetics.Sarah Adelaide Crawford is professor of genetics at Southern Connecticut State University. Dr. Crawford received a Ph.D. from Columbia University College of Physicians and Surgeons, an M.S. degree in biochemistry from Princeton University, and a B.S. degree from Marymount Manhattan College. She is director of the Cancer Biology Research Laboratory and the recently opened the Autism Research Laboratory at the Southern Connecticut State University.
Keywords: dept.bio

Genome sequences of Chancellor, Mitti, and Wintermute, three subcluster K4 phages isolated using Mycobacterium smegmatis mc ^2 155 - Edgington, Nicholas P.; Voshell, Stephanie M.; Ware, Vassie C.; Akoto, Francis F.; Alhout, Alexa A.; Atwal, Gurvina J.; Balyozian, John B.; Cadieux, Zachary A.; Chop, Brianna M.; Cresawn, Steven G.; Cudkevich, Netta; Faltine-Gonzalez, Dylan Z.; et al. (Genome Announcements, 2017)
Mycobacteriophages Chancellor, Mitti, and Wintermute infect Mycobacterium smegmatis mc2155 and are closely related to phages Cheetobro and Fionnbharth in subcluster K4. Genome sizes range from 57,697 bp to 58,046 bp. Phages are predicted to be temperate and to infect the pathogen Mycobacterium tuberculosis. © 2017 Edgington et al.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-598-311-527-674, pop00117 tex.type: [object Object]
Keywords: Mycobacterium smegmatis; Mycobacterium tuberculosis; dept.bio; genome size; infectious agent; mycobacteriophage; nonhuman

Environmental exposure does not explain putative maladaptation in road-adjacent populations. - Brady, Steven P (Oecologia, 2017)
While the ecological consequences of roads are well described, little is known of their role as agents of natural selection, which can shape adaptive and maladaptive responses in populations influenced by roads. This knowledge gap persists despite a growing appreciation for the influence of evolution in human-altered environments. There, insights indicate that natural selection typically results in local adaptation. Thus, populations influenced by road-induced selection should evolve fitness advantages in their local environment. Contrary to this expectation, wood frog tadpoles from roadside populations show evidence of a fitness disadvantage, consistent with local maladaptation. Specifically, in reciprocal transplants, roadside populations survive at lower rates compared to populations away from roads. A key question remaining is whether roadside environmental conditions experienced by early stage embryos induce this outcome. This represents an important missing piece in evaluating the evolutionary nature of this maladaptation pattern. Here, I address this gap using a reciprocal transplant experiment designed to test the hypothesis that embryonic exposure to roadside pond water induces a survival disadvantage. Contrary to this hypothesis, my results show that reduced survival persists when embryonic exposure is controlled. This outcome indicates that the survival disadvantage is parentally mediated, either genetically and/or through inherited environmental effects. This result suggests that roadside populations are either truly maladapted or potentially locally adapted at later life stages. I discuss these interpretations, noting that regardless of mechanism, patterns consistent with maladaptation have important implications for conservation. In light of the pervasiveness of roads, further resolution explaining maladaptive responses remains a critical challenge in conservation.
14 citations (Crossref) [2023-10-31] Place: Germany Brady, Steven P. School of Forestry & Environmental Studies, Yale University, 370 Prospect Street, New Haven, CT, 06511, USA. brady.steven@gmail.com. Brady, Steven P. Biology Department, Southern Connecticut State University, New Haven, CT, 06515, USA. brady.steven@gmail.com.
Keywords: *Adaptation; Physiological; *Environmental Exposure; *Ranidae; *Selection; Genetic; Acclimatization; Adaptation; Physiological; Amphibia; Amphibians; Animals; Contemporary evolution; Environmental Exposure; Inherited environmental effects; Larva; Local adaptation; Rana sylvatica; Ranidae; Ranidae/ph [Physiology]; Runoff; Selection; Genetic; acclimatization; adaptation; amphibian; animal; dept.bio; embryonic development; environmental conditions; environmental effect; environmental exposure; evolutionary biology; fitness; frog; genetic selection; larva; local adaptation; natural selection; physiology; pond; population type; roadside environment; runoff; survival

Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
6 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival

How valid are old species lists? How archived samples can be used to update Ephemeroptera biodiversity information for northern Canada - Giberson, Donna J.; Burian, Steven K. (The Canadian Entomologist, 2017)
Abstract Broad-scale aquatic insect ecological studies are an important potential source of biodiversity information, though taxa lists may contain outdated names or be incompletely or incorrectly identified. We re-examined over 12 000 archived Ephemeroptera (mayfly) specimens from a large environmental assessment project (Mackenzie Valley pipeline study) in Yukon and the Northwest Territories, Canada (1971–1973) and compared the results to data from five recent (post-2000) collecting expeditions. Our goals were to update the species list for Ephemeroptera for Yukon and the Northwest Territories, and to evaluate the benefits of retaining and re-examining ecological samples to improve regional biodiversity information, particularly in isolated or inaccessible areas. The original pipeline study specimen labels reported 17 species in 25 genera for the combined Yukon and Northwest Territories samples, of which six species and 15 genera are still valid. Re-examination of specimens resulted in 45 species in 29 genera, with 14 and seven newly recorded species for Northwest Territories and Yukon, respectively. The recent collecting resulted in 50 species, 29 of which were different from the pipeline study, and five of which were new territorial records (Northwest Territories: four species; Yukon: one species). Re-examination of archived ecological specimens provides a cost-effective way to update regional biodiversity information.
4 citations (Crossref) [2023-10-31]
Keywords: Canada; Ephemeroptera; Hexapoda; Mackenzie Valley; Northwest Territories; Yukon Territory; aquatic organism; biodiversity; dept.bio; environmental assessment; information; mayfly; new record; sampling; species inventory

Range extensions for recently described North American species of Acentrella Bengtsson (Insecta: Ephemeroptera: Baetidae) - Webb, Jeffrey M.; Burian, Steven K. (Check List, 2017)
New state records are provided for two recently described species of North American Acentrella Bengtsson, 1912. Acentrella nadineae McCafferty, Waltz & Webb, 2009 is newly reported from Connecticut, Massachusetts, and Minnesota, and A. rallatoma Burian & Myers, 2011 is reported from Minnesota.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-027-562-874-776, pop00306 tex.type: [object Object]
Keywords: Mayfly; Nearctic; New records; Range extension; dept.bio; mayfly; new records; range extension

Antimicrobial evaluation of 5-substituted aryl 1H-tetrazoles - Feinn, Liana; Dudley, Joshua; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2017)
Background: Tetrazole derivatives such as 1-substituted dinitrobenzyl tetrazoles and their oxa and selanyl analogs have previously been studied against drug-susceptible and multidrugresistant mycobacteria. In addition, other tetrazole derivatives have been shown to inhibit CTX-M class A μ-lactamases. Objective: To study the antibacterial activity of 5-substituted aryl 1H-tetrazole derivatives. Methods: The antibacterial activity of several known 5-substituted aryl 1H-tetrazole derivatives was evaluated against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The activity was assessed by determining the minimum inhibitory concentration of these tetrazole derivatives and comparing them to the known antibiotics amoxicillin, trimethoprim and sulfamethoxazole. Results: Some derivatives showed significant antibacterial activity with the most active derivatives exhibiting a minimum inhibitory concentration (MIC) of 125-250 μg/mL against Staphylococcus aureus and Escherichia coli. Using some of these tetrazole compounds in combination with trimethoprim led to a synergistic effect that gave MIC values ranging from 0.24-1.95 μg/mL against Escherichia coli and 3.91-31.3 μg/mL against Staphylococcus aureus. The tetrazole derivatives were prepared in an isopropanol/water mixture using microwave heating at 160 °C for 1h. The cycloaddition between organonitriles and sodium azide was catalyzed by indium chloride. Conclusion: This study shows a significant synergistic effect between the tetrazole compounds tested and trimethoprim which could be used to potentially develop new antibacterial agents. © 2017 Bentham Science Publishers.
4 citations (Crossref) [2023-10-31]
Keywords: 1; 4 di(tetrazol 5 yl)benzene; 2 propanol; 4 acetylbenzonitrile; 4 acetylbenzotetrazole; 4 bromobenzotetrazole; 5 substituted aryl tetrazole derivative; 5-substituted 1H-tetrazoles; Antibacterial activity; Antimicrobial activity; Article; Escherichia coli; Indium chloride; Microwave chemistry; Pseudomonas aeruginosa; Staphylococcus aureus; [2 + 3] cycloaddition; amoxicillin; antibacterial activity; antibiotic agent; catalysis; clinical assessment; comparative study; controlled study; cycloaddition; dept.bio; dept.che; drug effect; drug screening; drug structure; indium chloride; microwave cooking; minimum inhibitory concentration; nonhuman; peer-reviewed; priority journal; reaction analysis; sodium azide; sulfamethoxazole; tetrazole derivative; trimethoprim; unclassified drug; water

Winter Quiescence, Growth Rate, and the Release from Competition in the Temperate Scleractinian Coral Astrangia poculata (Ellis & Solander 1786) - Grace, Sean (Northeastern Naturalist, 2017)
I examined winter quiescence (dormancy), growth rate, and competition in the scleractinian coral Astrangia poculata (Northern Star-coral) at an intertidal and a subtidal site in Rhode Island. I observed the onset, duration, and cessation of quiescence from November 2013 to May 2014 and noted when coral tentacles no longer exhibited tactile responses, which I used as a proxy for quiescence. Results demonstrated that intertidal corals entered quiescence in December 2013, when air/water temperatures ranged from 0.71 °C to 5.7 °C, whereas subtidal populations entered quiescence in January when water temperatures ranged from 3.4 °C to 4.3 °C. Corals exited quiescence at similar temperatures (6.0–8.5 °C), again doing so earlier in the intertidal than subtidal populations (April and May 2014, respectively). Corals at both sites grew (added polyps) over the course of the study, but during quiescence, growth ceased in subtidal corals, and intertidal corals lost peripheral polyps. Competitive interactions between Northern Star-coral and the tunicate Didemnum vexillum (Carpet Tunicate) decreased during quiescence with a corresponding increase in “halo” width around each coral. I observed no change in halo-width between coral and the sponge Cliona celata (Red Boring Sponge). All corals examined exhibited winter quiescence, grew during the course of the study, and were released from competition with Carpet Sea-squirt Tunicate; no change in competition with Red Boring Sponge was observed.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/116-846-890-414-593, pop00163 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
175 citations (Crossref) [2023-10-31] Place: England Dedrick, Rebekah M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Bustamante, Carlos A Guerrero. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Reyes, Juan C Cervantes. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Adair, Tamarah. Department of Biology, Baylor University, Waco, Texas 76798, USA. Alvey, Richard. Biology Department, Illinois-Wesleyan University, Bloomington, Illinois 61702, USA. Bonilla, J Alfred. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Bricker, Jerald S. Biology Department, Nebraska-Wesleyan University, Lincoln, Nebraska 68504, USA. Brown, Bryony R. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Byrnes, Deanna. Biology Department, Carthage College, Kenosha, Wisconsin 53140, USA. Cresawn, Steven G. Biology Department, James Madison University, Harrisonburg, Virginia 22807, USA. Davis, William B. School of Molecular Biosciences, Washington State University Pullman, Washington 99164, USA. Dickson, Leon A. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Edgington, Nicholas P. Biology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Findley, Ann M. Biology, School of Sciences, University of Louisiana at Monroe, Monroe, Louisiana 71209, USA. Golebiewska, Urszula. Biological Sciences and Geology, Queensborough Community College, Bayside, New York 11364, USA. Grose, Julianne H. Biology Department, Brigham Young University, Provo, Utah 84602, USA. Hayes, Cory F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Hughes, Lee E. Biological Sciences, University of North Texas, Denton, Texas 76203, USA. Hutchison, Keith W. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Isern, Sharon. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Johnson, Allison A. Biology Department, Virginia Commonwealth University, Richmond, Virginia 23284, USA. Kenna, Margaret A. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Klyczek, Karen K. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Mageeney, Catherine M. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Michael, Scott F. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Molloy, Sally D. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Montgomery, Matthew T. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Neitzel, James. Biology Department, The Evergreen State College, Olympia, Washington 98502, USA. Page, Shallee T. Division of Environmental and Biological Sciences, University of Maine-Machias, Machias, Maine 04654, USA. Pizzorno, Marie C. Biology Department, Bucknell University, Lewisburg, Pennsylvania 17837, USA. Poxleitner, Marianne K. Biology Department, Gonzaga University, Spokane, Washington 99258, USA. Rinehart, Claire A. Biology Department, Western Kentucky University, Bowling Green, Kentucky 42101, USA. Robinson, Courtney J. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Rubin, Michael R. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Teyim, Joseph N. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Vazquez, Edwin. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Ware, Vassie C. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Washington, Jacqueline. Department of Biology and Chemistry, Nyack College, Nyack, New York 10960, USA. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA; Viral; DNA; Viral/ge [Genetics]; Genetic Variation; Genome; Bacterial; Genome; Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3'; 5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Physiological consequences of exposure to salinized roadside ponds on wood frog larvae and adults - Hall, Emily M.; Brady, Steven P.; Mattheus, Nichole M.; Earley, Ryan L.; Diamond, Molly; Crespi, Erica J. (Biological Conservation, 2017)
40 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Evolutionary toxicology: Toward a unified understanding of life's response to toxic chemicals. - Brady, Steven P; Monosson, Emily; Matson, Cole W; Bickham, John W (Evolutionary Applications, 2017)
45 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. The Ronin Institute for Independent Scholars and Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole W. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station College Station TX USA.
Keywords: dept.bio; peer-reviewed

Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
42 citations (Crossref) [2023-10-31]
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-040-409-668-282, pop00101 tex.type: [object Object]
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff

Autism risk: What do vaccines have to do with - Crawford, Sarah Adelaide (Academic Journal of Pediatrics & Neonatology, 2017)
Keywords: dept.bio; ⚠️ Invalid DOI

Using time dynamically in static intervals: Does it close the achievement gap? - Grace, Lori (Learning Environments Research, 2017)
A mixed-methods study was undertaken with 118 biology students in two urban high schools. A Student-Centered Adaptable Learning Environment (SCALE) was created to improve engagement from affective and cognitive perspectives using choice, creativity and technological allowances. Results demonstrated that fast and slow learners are generally separated by about 30 min in terms of inputting speeds, but can be as much as 65 min apart from one another. Given that traditional classrooms afford students only 45 min in which to learn, static time could have become a source of inequity in public schools. SCALE optimally allowed for the dynamic use of time in constrained periods, therefore reducing and even eliminating any negative relationships between speed of learning and resultant achievement gains in the block setting. Especially benefitting from their ability to maneuver were the slowest learners, who showed the largest achievement improvements in either time interval amongst ability groupings. As learning speed can be the most critical contributing component of resultant educational outcomes, providing students the ability to use time dynamically should be considered as a feasible solution to helping teachers reestablish equity in mixed-ability classrooms in public schools. © 2017, Springer Science+Business Media Dordrecht.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-365-031-456-996 tex.type: [object Object]
Keywords: Cognitive levelling; Dynamic time; Educational technology; Learning equity; Learning speed gap; Psychosocial learning environments; dept.bio